Polymers based on ionic monomers, compositions containing the same, methods for preparing the same, and uses thereof in electrochemical applications
Patent Information
- Application Number
- KR1020227029291
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-05
- Filing Date
- 2021-01-22
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2041-01-22
Smart Images

Figure 112022088699109-PCT00109_ABST
Abstract
Description
Technology Field
[0001] Related applications
[0002] This application claims priority to U.S. provisional patent application No. 62 / 965,560 filed January 24, 2020, U.S. provisional patent application No. 62 / 977,521 filed February 17, 2020, and European patent application No. 20 206 000.0 filed November 2, 2020, the contents of which are incorporated herein by reference in their entirety.
[0003] Technology field
[0004] The present invention relates to polymers and the use thereof in electrochemical applications. More specifically, the present invention relates to solid polymer electrolytes, polymer compositions, solid polymer electrolyte compositions, methods for manufacturing the same, and the use thereof in electrochemical cells, electrochromic devices, supercapacitors or electrochemical capacitors, in particular in all-solid-state batteries. Background Technology
[0005] Solid polymer electrolytes are promising materials for various technological applications because they enable the development of all-solid-state electrochemical systems that are substantially safer, lighter, more flexible, and more efficient compared to electrolytes based on the use of liquid electrolytes.
[0006] Despite the significant advantages of solid polymer electrolytes, their use remains limited primarily due to restricted electrochemical stability, low transport number, and relatively low ionic conductivity. Indeed, conventional solid-state polymer electrolytes generally operate at high voltages (≥ 4 V vs. Li / Li). + Because it does not support ), the electrochemical stability window of conventional solid-state polymer electrolytes is still relatively limited.
[0007] Furthermore, conventional solid polymer electrolytes, such as those based on poly(ethylene oxide) (PEO), face ionic conductivity issues at ambient temperatures. For example, the ionic conductivity of PEO is 10 when the polymer is in a molten state. -3 S·cm -1 It is the size of (Hallinan et al ., Annual review of materials research 43 (2013): 503-525). However, ion transport occurs mainly in the amorphous phase and decreases in the crystalline phase, resulting in a significant decrease in the ionic conductivity of PEO-based polymers. Indeed, the ionic conductivity of PEO-based polymers decreases significantly at operating temperatures below the melting point (Armand, M. Solid State Ionics 9 (1983): 745-754). In addition, the degree of crosslinking of PEO-based polymers is associated with problems of electrochemical stability and low ionic conductivity, particularly due to reduced segment mobility.
[0008] General approaches to address the problem of low ionic conductivity include modifying the polymer structure to reduce crystallinity by, for example, using branched or block-type PEO-based polymers containing monomer units that lower the crystallization temperature or glass transition temperature, or by increasing the ion transport rate. Another strategy used to address this problem involves incorporating nanoscale ceramic fillers, such as titanium dioxide (TiO2), alumina (Al2O3), silicon dioxide (SiO2), and lithium aluminate (LiAlO2) nanoparticles, into PEO-based polymers to improve mechanical strength. However, the presence of these fillers can contribute to a decrease in the electrochemical and / or mechanical properties of the polymer.
[0009] Therefore, there is a need to develop a solid polymer electrolyte that eliminates one or more of the disadvantages of conventional solid polymer electrolytes.
[0010] According to one embodiment, the present invention relates to an ionic polymer comprising at least one repeating unit comprising a reaction product between at least one compound of Formula 1 comprising at least two functional groups and a metal bis(halosulfonyl)imide of Formula 2:
[0011]
[0012] Here, A is a linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkylene oxy C1-C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1-C 10 A substituted or unsubstituted organic group selected from alkylenes, linear or branched polyethers, and linear or branched polyesters;
[0013] X1 and X2 are functional groups selected independently and in each occurrence from hydroxyl groups, thiol groups, and amine groups;
[0014] X3 and X4 are each independently halogen atoms selected from F, Cl, Br, and I; and
[0015] M n+ Ga Na + , K + , Li + , Ca 2+ and Mg 2+ It is an alkali metal ion or alkaline earth metal ion selected from a group of ions.
[0016] In one embodiment, the compound of Formula 1 is selected from glycerol, alkanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol, 1,2-butanediol, 2,3-butanediol, 1,3-butanediol, 1,2-pentanediol, ethohexadiol, p-methane-3,8-diol, 2-methyl-2,4-pentanediol, polycaprolactone diol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, polyethylene glycol, 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediol, other similar glycols and diols, and combinations of at least two of these.
[0017] In another embodiment, the compound of Formula 1 is an alkanediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,8-octanediamine, 1,2-propanediamine, 1,2-butanediamine, 2,3-butanediamine, 1,3-butanediamine, 1,2-pentanediamine, 2,4-diamino-2-methylpentane, ethylenediamine, 1,8-diamino-3,6-dioxaoctane, 1,11-diamino-3,6,9-trioxawundecane, 4,9-dioxa-1,12-dodecanediamine, 1,14-diamino-3,6,9,12-tetraoxatetradecane, poly(ethylene glycol)diamine, D, ED, or EDR commercialized under the trademark JEFFAMINE® It is selected from series products, other similar diamines, and combinations of at least two of these.
[0018] In another embodiment, A is an optionally substituted linear or branched C1-C 10 The compound of chemical formula 1, which is an alkylene, is the compound of chemical formula 3:
[0019]
[0020] Here, X1 and X2 are as defined in this specification;
[0021] R1 and R2 are independently and in each occurrence a halogen atom selected from hydrogen atoms, hydroxyl groups, thiol groups, amine groups, F, Cl, Br, and I, and C1-C 10 Alkyl, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-acrylate, aminocarbonyl-C1-C 10 Alkyl-methacrylate, aminocarbonyl-C1-C 10 Alkyl-acrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 Selected from linear or branched substituents selected from alkyl-acrylates; and
[0022] l is a number within the range of 1 to 10.
[0023] In another embodiment, A is linear or branched and optionally substituted poly(C1-C 10 Alkyleneoxy)C1-C 10 It is an alkylene, and the compound of chemical formula 1 is the compound of chemical formula 4:
[0024]
[0025] Herein, X1 and X2 are as defined in this specification; and
[0026] m is a number from 1 to 68.
[0027] In another embodiment, A is a linear or branched and optionally substituted polyether, and the compound of Formula 1 is a compound of Formula 5:
[0028]
[0029] Here, X1 and X2 are as defined in this specification;
[0030] R3, R4, and R5 independently and in each occurrence C1-C10 Selected from alkyl groups;
[0031] n, o, and p are selected such that the number average molecular weight of the polyether is from about 220 g / mol to about 2,000 g / mol, including upper and lower limits;
[0032] n and p are selected such that the sum (n + p) is approximately 1 to approximately 6; and
[0033] o is a number ranging from about 2 to about 39.
[0034] In another embodiment, R3, R4 and R5 are methyl groups.
[0035] In another embodiment, X1 and X2 are both amine groups.
[0036] In another embodiment, A is an optionally substituted aliphatic polyester such as polycaprolactone, and the compound of Formula 1 is a compound of Formula 7:
[0037]
[0038] Here, t and u are numbers within the range of 1 to 10.
[0039] According to another aspect, the present invention relates to an ionic polymer comprising at least one repeating unit of Formula 8(a) or a polymer of Formula 8(b):
[0040]
[0041] Here, A is independent and linear or branched C1-C in each occurrence 10 Alkylene, linear or branched C1-C 10 Alkylene oxy C1-C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1-C 10 A substituted or unsubstituted organic group selected from alkylenes, linear or branched polyethers, and linear or branched polyesters;
[0042] X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups;
[0043] R6 is selected from hydroxyl groups, thiol groups, amine groups, and R7-X5-A-X6- groups;
[0044] R7 independently produced acrylate, methacrylate, and C1-C in each occurrence. 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonyl-C1-C 10 Alkyl-methacrylate carbonyl-C1-C 10 Alkyl-acrylate, carbonyloxy-C1-C 10 Alkyl-methacrylate, carbonyloxy-C1-C 10 Alkyl-acrylate, carbonylamino-C1-C 10 Alkyl-methacrylate and carbonylamino-C1-C 10 A crosslinkable group selected from alkyl-acrylates;
[0045] M n+ This Na + , K + , Li + , Ca 2+ and Mg 2+ It is an alkali metal ion or alkaline earth metal ion selected from the group consisting of ions; and
[0046] v is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0047] According to another aspect, the present invention relates to an ionic polymer comprising at least one repeating unit of Formula 9:
[0048]
[0049] Here, M n+ This Na + , K + , Li + , Ca 2+ and Mg2+ It is an alkali metal ion or alkaline earth metal ion selected from the group consisting of ions;
[0050] X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups;
[0051] R1 and R2 are independently and in each occurrence a halogen atom selected from hydrogen atoms, hydroxyl groups, thiol groups, amine groups, F, Cl, Br, and I, and C1-C 10 Alkyl, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-acrylate, aminocarbonyl-C1-C 10 Alkyl-methacrylate, aminocarbonyl-C1-C 10 Alkyl-acrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 Selected from linear or branched substituents selected from alkyl-acrylates;
[0052] l is a number within the range of 1 to 10; and
[0053] w is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0054] According to another aspect, the present invention relates to an ionic polymer comprising at least one repeating unit of Formula 10:
[0055]
[0056] Here, M n+ This Na + , K + , Li + , Ca 2+ and Mg 2+It is an alkali metal ion or alkaline earth metal ion selected from the group consisting of ions;
[0057] X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups;
[0058] m is a number within the range of 1 to 68; and
[0059] x is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0060] According to another aspect, the present invention relates to an ionic polymer comprising at least one repeating unit of Formula 11:
[0061]
[0062] Here, M n+ This Na + , K + , Li + , Ca 2+ and Mg 2+ It is an alkali metal ion or alkaline earth metal ion selected from the group consisting of ions;
[0063] X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups;
[0064] R3, R4, and R5 independently and in each occurrence C1-C 10 Selected from alkyl groups;
[0065] n and p are selected such that the sum (n + p) is approximately 1 to approximately 6;
[0066] o is a number from about 2 to about 39; and
[0067] y is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0068] According to another aspect, the present invention relates to an ionic polymer comprising at least one repeating unit of Formula 12:
[0069]
[0070] Here, M n+ This Na + , K + , Li + , Ca 2+ and Mg 2+ It is an alkali metal ion or alkaline earth metal ion selected from the group consisting of ions;
[0071] t and u are numbers from 1 to 10; and
[0072] z is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0073] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 13:
[0074]
[0075] Here, x is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0076] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 14:
[0077]
[0078] Here, x is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0079] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 15:
[0080]
[0081] Here, X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups; and
[0082] x is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0083] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 16:
[0084]
[0085] Here, X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups; and
[0086] x is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0087] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 17:
[0088]
[0089] Here, X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups; and
[0090] x is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0091] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 18:
[0092]
[0093] Here, X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups; and
[0094] x is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0095] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 19:
[0096]
[0097] Here, w is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0098] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 20:
[0099]
[0100] Here, w is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0101] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 21:
[0102]
[0103] Here, n and p are selected such that the sum (n + p) is approximately 1 to approximately 6;
[0104] o is a number from about 2 to about 39; and
[0105] y is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0106] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 22:
[0107]
[0108] Here, n and p are selected such that the sum (n + p) is approximately 1 to approximately 6;
[0109] o is a number from about 2 to about 39; and
[0110] y is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0111] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 23:
[0112]
[0113] Here, n and p are selected such that the sum (n + p) is approximately 1 to approximately 6;
[0114] o is a number from about 2 to about 39; and
[0115] y is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0116] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 24:
[0117]
[0118] Here, n and p are selected such that the sum (n + p) is approximately 1 to approximately 6;
[0119] o is a number from about 2 to about 39; and
[0120] y is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0121] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 25:
[0122]
[0123] Here, n and p are selected such that the sum (n + p) is approximately 1 to approximately 6;
[0124] o is a number from about 2 to about 39; and
[0125] y is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0126] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 26:
[0127]
[0128] Here, w and x are numbers selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0129] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 27:
[0130]
[0131] Here, w and x are numbers selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0132] According to another aspect, the present invention relates to an ionic polymer comprising at least one fragment of Formula 28:
[0133]
[0134] Here, w and x are numbers selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0135] According to another aspect, the present invention relates to a polymer composition comprising at least one ionic polymer as defined herein.
[0136] According to one embodiment, the polymer composition further comprises at least one additional component or additive. According to one example, the additional component or additive is selected from ion conductors, inorganic particles, glass particles, ceramic particles, salts and other similar additives, or a combination of at least two of these. According to another example, the additional component or additive is a filler additive selected from titanium dioxide (TiO2), alumina (Al2O3), silicon dioxide (SiO2) particles or nanoparticles.
[0137] In another embodiment, the polymer composition is used in an electrochemical cell. In another embodiment, the polymer composition is a solid polymer electrolyte composition. In another embodiment, the polymer composition is a binder for an electrode material. In another embodiment, the polymer composition is used in a supercapacitor. According to one example, the supercapacitor is a carbon-carbon supercapacitor. In another embodiment, the polymer composition is used in an electrochromic material.
[0138] According to another aspect, the present invention relates to a solid polymer electrolyte composition comprising a polymer composition as defined herein.
[0139] In another embodiment, the solid polymer electrolyte composition further comprises at least one salt. According to one example, the salt is an ionic salt selected from lithium salt, sodium salt, potassium salt, calcium salt, and magnesium salt.
[0140] In another embodiment, the solid polymer electrolyte composition further comprises at least one additional component or additive. According to one example, the additional component or additive is selected from ion conductor materials, inorganic particles, glass particles, ceramic particles, a combination of at least two of these, and other similar additives.
[0141] According to another aspect, the present invention relates to a solid polymer electrolyte comprising a solid polymer electrolyte composition as defined in this specification.
[0142] According to another aspect, the present invention relates to an electrode material comprising an electrochemically active material and a polymer composition as defined herein. In one embodiment, the polymer composition is a binder.
[0143] In another embodiment, the electrochemically active material is in the form of particles. According to one example, the electrochemically active material is selected from metal oxide, lithium metal oxide, metal phosphate, lithiated metal phosphate, titanate, and lithium titanate. According to another example, the metal of the electrochemically active material is selected from titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), chromium (Cr), copper (Cu), antimony (Sb), and combinations of at least two of these.
[0144] In another embodiment, the electrode material further comprises at least one electrically conductive material. According to one example, the electrically conductive material is selected from carbon black, acetylene black, graphite, graphene, carbon fiber, carbon nanofiber, carbon nanotube, and combinations of at least two of these.
[0145] In another embodiment, the electrode material further comprises at least one additional component or additive. According to one example, the additional component or additive is selected from ion conductors, inorganic particles, glass or ceramic particles, nanoceramics, salts, and other similar additives. According to another example, the additional component or additive is selected from Al2O3, TiO2, and SiO2.
[0146] In another embodiment, the electrode material is a positive electrode material. In another embodiment, the electrode material is a negative electrode material. According to one example, the electrochemically active material is lithium titanate or carbon-coated lithium titanate.
[0147] According to another aspect, the present invention relates to an electrode comprising an electrode material as defined in this specification on a current collector.
[0148] According to another aspect, the present invention relates to an electrochemical cell comprising a cathode, an anode, and an electrolyte, wherein at least one of the cathode, the anode, and the electrolyte comprises a polymer composition as defined herein.
[0149] According to another aspect, the present invention relates to an electrochemical cell comprising a cathode, an anode, and an electrolyte, wherein at least one of the cathode and the anode is as defined herein.
[0150] According to another aspect, the present invention relates to an electrochemical cell comprising a cathode, an anode, and a solid polymer electrolyte as defined herein.
[0151] According to another aspect, the present invention relates to an electrochemical capacitor comprising at least one electrochemical cell as defined in this specification.
[0152] In one embodiment, the electrochemical capacitor is a battery selected from a lithium battery, a lithium-ion battery, a sodium battery, a sodium-ion battery, a magnesium battery, and a magnesium-ion battery. According to one example, the battery is a lithium battery or a lithium-ion battery.
[0153] According to another aspect, the present invention relates to a method for preparing a polymer or a polymer composition as defined herein, and the method comprises the following steps:
[0154] (i) a step of preparing a metal bis(halosulfonyl)imide of Formula 2; and
[0155] (ii) a step of reacting at least one compound of Formula 1, comprising at least two functional groups as defined herein, with the metal bis(halosulfonyl)imide of Formula 2.
[0156] In another embodiment, the method further comprises the step of preparing bis(halosulfonyl)imide. According to one example, the step of preparing bis(halosulfonyl)imide is carried out by a reaction between a sulfamic acid and a halosulfonic acid in the presence of at least one halogenating agent.
[0157] According to one example, the halogenating agent is selected from phosphorus trichloride, phosphorus pentachloride, thionyl chloride, thionyl fluoride, phosphorus oxychloride, and oxalyl chloride. According to one example, the halogenating agent is thionyl chloride. According to another example, the halosulfonic acid is chlorosulfonic acid.
[0158] In another embodiment, the step of preparing bis(halosulfonyl)imide is carried out at a temperature within a range of about 60°C to about 150°C, or about 70°C to about 145°C, or about 80°C to about 140°C, or about 90°C to about 100°C, or about 110°C to about 140°C, or about 120°C to about 140°C, or about 125°C to about 140°C, or about 125°C to about 135°C, including upper and lower limits.
[0159] In another embodiment, the bis(halosulfonyl)imide is the bis(chlorosulfonyl)imide.
[0160] In another embodiment, the step of preparing a metal bis(halosulfonyl)imide is optionally carried out by a metallization reaction between the bis(halosulfonyl)imide and at least one metallizing agent in the presence of a solvent.
[0161] According to one example, the metallizing agent comprises an alkali metal or alkaline earth metal selected from lithium, sodium, potassium, calcium, and magnesium. According to one example, the metallizing agent comprises lithium hydroxide, lithium carbonate, lithium bicarbonate, lithium hydride, lithium chloride, lithium bromide, lithium iodide, and the chemical formula RCO2Li (where R is a linear or branched C1-C 10 The lithiating agent is selected from lithium carboxylates, lithium oxalates, and metallic lithium (which are alkyl groups or aromatic hydrocarbons). According to another example, the lithiating agent is lithium chloride.
[0162] In another embodiment, the solvent is selected from N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethylacetamide, tetrachloromethane, chloroform, acetonitrile, tetrahydrofuran, and miscible combinations of at least two of these. According to one example, the solvent is N,N-dimethylformamide.
[0163] In another embodiment, the step of preparing the metal bis(halosulfonyl)imide of Formula 2 is carried out at a temperature within the range of about 20°C to about 150°C, or about 30°C to about 135°C, or about 40°C to about 130°C, or about 50°C to about 125°C, or about 60°C to about 120°C, or about 70°C to about 115°C, or about 80°C to about 110°C, or about 90°C to about 105°C, including upper and lower limits.
[0164] In another embodiment, the step of preparing the metal bis(halosulfonyl)imide is performed for a time within the range of about 10 hours to about 48 hours, or about 10 hours to about 24 hours, or about 12 hours to about 24 hours, including upper and lower limits.
[0165] In another embodiment, the step of reacting at least one compound of Formula 1 containing at least two functional groups with the metal bis(halosulfonyl)imide of Formula 2 is a polymerization step. According to one example, the polymerization is carried out by polycondensation. For example, the polymerization is carried out by polyesterization. According to one example, the polyesterization is carried out by a Fischer esterification reaction or a Steglich esterification reaction.
[0166] In another embodiment, the step of reacting at least one compound of Formula 1 comprising at least two functional groups with the metal bis(halosulfonyl)imide of Formula 2 is carried out in the presence of a solvent. According to one example, the solvent is selected from N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethylacetamide, tetrachloromethane, chloroform, acetonitrile, tetrahydrofuran, and miscible combinations of at least two of these. For example, the solvent is N,N-dimethylformamide.
[0167] In another embodiment, the polymerization step is carried out in the presence of at least one base and optionally at least one polymerization catalyst and / or at least one co-catalyst and / or optionally at least one acylation catalyst.
[0168] In another embodiment, the polymerization catalyst is selected from the group consisting of acidic catalysts, nucleophilic catalysts, and boron-based catalysts.
[0169] In another embodiment, the nucleophilic catalyst is selected from the group consisting of 4-dimethylaminopyridine, pyridine, and other pyridine derivatives.
[0170] In other embodiments, the boron-based catalyst is a boric acid (3 OH groups)-based catalyst, a boronic acid (2 OH groups)-based catalyst, or a boric acid (1 OH group)-based catalyst. For example, the polymerization catalyst is selected from diarylboric acids of the formula Ar2BOH (where Ar is an aryl group), diphenylboric acid, phenylboric acid, trifluorophenylboric acid, 9H-9-bora-10-thianthracen-9-ol, 10H-phenoxaborinine-10-ol, boron tribromide, boron trichloride, acyl fluoroborates, triethyloxonium fluoroborate, boron trifluoride etherate, boron trifluoride, tris(pentafluorophenyl)borane, and other similar boron-derived catalysts, or, if compatible, a combination of at least two of these.
[0171] In another embodiment, the base is selected from triethylamine, N,N-diisopropylethylamine, pyridine, and pyridine derivatives. According to one example, the base is triethylamine.
[0172] In another embodiment, the method further comprises a post-functionalization or post-polymerization modification step. According to one example, the post-functionalization or post-polymerization modification step is performed to introduce at least one crosslinkable functional group. According to one example, the post-functionalization or post-polymerization modification step is performed by reacting at least one functional group with a precursor of at least one crosslinkable functional group. For example, the crosslinkable functional group is an acrylate, methacrylate, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-acrylate, aminocarbonyl-C1-C 10 Alkyl-methacrylate aminocarbonyl-C1-C 10 Alkyl-acrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylate, oxycarbonylamino-C1-C 10 Alkyl-acrylate, carbonyloxy-C1-C 10 Alkyl-methacrylate, carbonyloxy-C1-C 10 Alkyl-acrylate, carbonylamino-C1-C 10 Alkyl-methacrylate and carbonylamino-C1-C 10 It is selected from alkyl-acrylates.
[0173] In another embodiment, the method further includes a separation or purification step. According to one example, the separation or purification step is performed by liquid chromatography or filtration.
[0174] In another embodiment, the method further comprises the step of coating a polymer composition. According to one example, the coating step is carried out by at least one method selected from doctor blade coating, comma coating, reverse-comma coating, printing, gravure coating, and slot-die coating.
[0175] In another embodiment, the method further includes a step of drying the polymer composition to remove any residual solvent and / or water. According to one example, the step of drying the polymer composition and the step of coating the polymer composition are performed simultaneously.
[0176] In another embodiment, the method further comprises a crosslinking step. For example, the crosslinking step is carried out by UV irradiation, heat treatment, microwave irradiation, under an electron beam, gamma ray irradiation, or X-ray irradiation. The crosslinking step may be carried out in the presence of at least one crosslinking agent, a thermal initiator, a photoinitiator (e.g., a UV initiator), a catalyst, a plasticizer, or a combination of at least two of these. Brief explanation of the drawing
[0177] Figure 1 is a chromatogram obtained by stereoexclusion chromatography (SEC) for polymer 2 as described in Example 3(b). FIG. 2 shows the proton nuclear magnetic resonance obtained for polymer 2 as described in Example 3(b) ( 1 This is the H NMR spectrum. FIG. 3 is a graph showing the results of differential scanning calorimetry (DSC) analysis obtained for polymer 2 as described in Example 3(b). Figure 4 is a chromatogram obtained by stereoexclusion chromatography for polymer 4 as described in Example 3(d). Figure 5 is the proton nuclear magnetic resonance spectrum of the polymer obtained by the polymerization of diethyl glycol and lithium bis(chlorosulfonyl)imide as described in Example 3(e). Figure 6 is the proton nuclear magnetic resonance spectrum obtained for polymer 5 as described in Example 3(e). FIG. 7 shows the carbon-13 nuclear magnetic resonance obtained for polymer 5 as described in Example 3(e). 13This is the C NMR spectrum. FIG. 8 shows the fluorine nuclear magnetic resonance obtained for polymer 5 as described in Example 3(e). 19 This is the F NMR spectrum. FIG. 9 is a graph showing the results of differential scanning calorimetry obtained for polymer 5 as described in Example 3(e). FIG. 10 shows the temperature (1000 / T, K) for cell 1 as described in Example 4(h). -1 Ionic conductivity (S·cm) as a function of ) -1 This is a graph showing the results of ). FIG. 11 shows the temperature (1000 / T, K) for cell 2 as described in Example 4(h). -1 Ionic conductivity (S·cm) as a function of ) -1 This is a graph showing the results of ). FIG. 12 shows the temperature (1000 / T, K) for cell 3 as described in Example 4(h). -1 Ionic conductivity (S·cm) as a function of ) -1 This is a graph showing the results of ). FIG. 13 shows the temperature (1000 / T, K) for cell 4 as described in Example 4(h). -1 Ionic conductivity (S·cm) as a function of ) -1 This is a graph showing the results of ). FIG. 14 shows the temperature (1000 / T, K) for cell 5 as described in Example 4(h). -1 Ionic conductivity (S·cm) as a function of ) -1 This is a graph showing the results of ). FIG. 15 shows the temperature (1000 / T, K) for cell 6 as described in Example 4(h). -1 Ionic conductivity (S·cm) as a function of ) -1 This is a graph showing the results of ). FIG. 16 is for cell 7 (comparison cell) (solid line) recorded at a scan rate of 0.067 mV / s as described in FIG. 5(c), and 2.7 V to 4.3 V versus Li / Li + This shows the cyclic voltammetry obtained for cell 8 (comparison cell) (dashed line) recorded at a scan rate of 0.05 mV / s. FIG. 17 shows 2.5 V to 5 V versus Li / Li as described in FIG. 5(c). + This shows the cyclic voltammetry obtained for cell 7 (comparison cell) recorded at a scan rate of 0.067 mV / s. FIG. 18 shows 2.5 V to 5 V versus Li / Li as described in FIG. 5(c). + The cyclic voltammetry obtained for cell 9 (solid line) and cell 10 (dashed line) recorded at a scan rate of 0.067 mV / s is shown. FIG. 19 shows 2.5 V to 5 V versus Li / Li as described in FIG. 5(c). + The cyclic voltammetry obtained for cell 7 (comparison cell) (two-dotted line), cell 10 (one-dotted line), cell 9 (dashed line), and cell 11 (comparison cell) (solid line), recorded at a scan rate of 0.067 mV / s, is shown. Specific details for implementing the invention
[0178] The following detailed descriptions and examples are for illustrative purposes only and should not be interpreted as limiting the scope of the invention.
[0179] The technical and scientific terms and expressions used herein have the same definitions as generally understood by a person skilled in the art of the present invention.
[0180] Nevertheless, definitions of some terms and expressions used here are given below.
[0181] Here, when "approximately" or the equivalent term "about" is used, it means roughly that vicinity or approximately that degree. For example, when "approximately" or "about" is used in relation to numerical values, they may vary higher or lower than the nominal value by an error of 10%. Additionally, these terms may account for, for example, rounding due to limitations of the measuring device or experimental error.
[0182] Where numerical ranges are referred to herein, the lower and upper limits of the range are always included in the definition, unless otherwise specified. Where numerical ranges are referred to in the present invention, all intermediate and sub-ranges and individual values included in these ranges are included in the definition.
[0183] For clarification, the expressions "monomer unit derived from" and equivalent expressions used herein refer to polymer repeating units obtained from the polymerization of polymerizable monomers.
[0184] The expression "repeating unit" used here refers to a sequence of repeating units that form part of a polymer chain.
[0185] With respect to polymer sequences, the term “fragment” as used herein refers to a part of a polymer comprising a repeating unit and optionally a terminal group.
[0186] The chemical structures described herein are schematically illustrated in accordance with the conventions of the art. Additionally, where a single atom, such as a carbon atom, appears to have an incomplete valence, it is assumed that the valence is satisfied by one or more hydrogen atoms, even if not explicitly illustrated.
[0187] For clarity, in this document, where a chemical formula represents a polymer repeating unit or fragment not defined as, for example, an OH group, an NH2 group, etc., the end of the linkage extending beyond the parenthesis(s) of the chemical formula, i.e.: or The group is not necessarily a methyl group but is defined as a residue of the polymer, and the definition of the group outside the parentheses is left open. For example, such a group may represent groups X1, X2, X3, X4, R6 or R7, residues of the initiator, or other polymer fragments as defined herein.
[0188] As used herein, the term "alkyl" means saturated hydrocarbons having 1 to 10 carbon atoms, including linear or branched alkyl groups. Non-limiting examples of alkyl groups may include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, isopropyl, tertiary-butyl, secondary-butyl, isobutyl, etc. Where the alkyl group is located between two functional groups, the term "alkyl" also includes alkylene groups such as methylene, ethylene, propylene, etc. The term "C m -C n alkyl" and "C m -C n "Alkylene" means an alkyl group or an alkylene group having carbon atoms ranging from the indicated number "m" to the indicated number "n".
[0189] As used herein, the term “aryl” refers to functional groups having aromatic properties and comprising rings having 6 to 14 cyclic atoms, preferably 6 cyclic atoms. The term “aryl” refers to both monocyclic and polycyclic conjugated systems. The term “aryl” also includes substituted or unsubstituted groups. Examples of aryl groups include, without limitation, phenyl, benzyl, phenethyl, 1-phenylethyl, tolyl, naphthyl, biphenyl, terphenyl, indenyl, benzocyclooctenyl, benzocycloheptenyl, azulenyl, acenaphthylenyl, fluorenyl, phenanthrenyl, anthracenyl, perylenyl, etc.
[0190] The present invention relates to an ionic polymer comprising at least one repeating unit comprising a reaction product between at least one compound of Formula 1 comprising at least two functional groups and a metal bis(halosulfonyl)imide of Formula 2:
[0191]
[0192] Here, A is a linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkylene oxy C1-C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1-C 10 A substituted or unsubstituted organic group selected from alkylenes, linear or branched polyethers, and linear or branched polyesters;
[0193] X1 and X2 are functional groups selected independently and in each occurrence from hydroxyl groups, thiol groups, and amine groups;
[0194] X3 and X4 are each independently halogen atoms selected from F, Cl, Br, and I; and
[0195] M n+ Ga Na + , K + , Li + , Ca2+ and Mg 2+ It is an alkali metal ion or alkaline earth metal ion selected from a group of ions.
[0196] According to one example, X1 and X2 may be functional groups selected independently and in each occurrence from a hydroxyl group (OH), a thiol group (SH), and a primary amine group (NH2). According to one variation of the subject, X1 and X2 may be functional groups selected independently and in each occurrence from a hydroxyl group and a primary amine group.
[0197] According to other examples, X1 and X2 can be identical, for example, X1 and X2 are both hydroxyl groups, both thiol groups, or both primary amine groups. According to one variation of the subject, X1 and X2 are both hydroxyl groups. According to another variation of the subject, X1 and X2 are both primary amine groups.
[0198] According to another example, X3 and X4 can be identical, for instance, X3 and X4 are both chlorine atoms.
[0199] According to another example, M n+ is Na + , K + and Li + It may be an alkali metal ion selected from a group consisting of ions, for example, M n+ is Li + It is an ion.
[0200] For example, X3 and X4 are both chlorine atoms and M n+ is Li + It is an ion, that is, the metal bis(halosulfonyl)imide of chemical formula 2 is lithium bis(chlorosulfonyl)imide.
[0201] According to another example, A is a linear or branched C2-C 10 Alkylene, linear or branched C2-C 10 Alkylene oxy C2-C10 Alkylene, linear or branched poly(C2-C 10 Alkyleneoxy)C2-C 10 It is a substituted or unsubstituted organic group selected from alkylene, linear or branched polyethers and linear or branched polyesters.
[0202] According to another example, A is a randomly substituted linear or branched C1-C 10 The compound of chemical formula 1, which is an alkylene, is the compound of chemical formula 3:
[0203]
[0204] Here, X1 and X2 are as defined in this specification;
[0205] R1 and R2 are independently and in each occurrence a halogen atom selected from hydrogen atoms, hydroxyl groups, thiol groups, amine groups, F, Cl, Br, and I, and C1-C 10 Alkyl, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-acrylate, aminocarbonyl-C1-C 10 Alkyl-methacrylate, aminocarbonyl-C1-C 10 Alkyl-acrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 Selected from linear or branched substituents selected from alkyl-acrylates; and
[0206] l is a number within the range of 1 to 10.
[0207] According to another example, R1 and R2 are independently and in each occurrence hydrogen atoms, hydroxyl groups, thiol groups, amine groups, fluorine atoms, and C1-C 10 Alkyl-acrylate, C1-C 10Alkyl-methacrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 It is selected from linear or branched substituents selected from alkyl-acrylates.
[0208] According to another example, R1 and R2 are independently and in each occurrence hydrogen atoms, hydroxyl groups, thiol groups, primary amine groups, fluorine atoms, and C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 It is selected from linear or branched substituents selected from alkyl-acrylates.
[0209] According to another example, l is a number within the range of 2 to 10.
[0210] According to another example, A is linear or branched and is an arbitrarily substituted poly(C1-C 10 Alkyleneoxy)C1-C 10 It is an alkylene, and for example, a compound of Formula 1 can be a compound of Formula 4:
[0211]
[0212] Herein, X1 and X2 are as defined in this specification; and
[0213] m is a number within the range of 1 to 68.
[0214] According to one variation of the subject, X1 and X2 are both hydroxyl groups or both amine groups, and the compounds of Formula 1 are Formula 4(a) or 4(b):
[0215]
[0216] Here, m is a number within the range of 1 to 6.
[0217] According to other variations of the subject, the compound of Formula 1 may be a JEFFAMINE® D series product, and the compound is Formula 4(c):
[0218]
[0219] Here, m is a number within the range of 1 to 68.
[0220] According to one example, a JEFFAMINE® D series product may be JEFFAMINE® D-230, where m is about 2.5 and the number average molecular weight of the polyether diamine is about 230 g / mol.
[0221] According to another example, a JEFFAMINE® D series product may be JEFFAMINE® D-400, where m is about 6.1 and the number average molecular weight of the polyether diamine is about 430 g / mol.
[0222] According to another example, the JEFFAMINE® D series product may be JEFFAMINE® D-2000, where m is about 33 and the number average molecular weight of the polyether diamine is about 2,000 g / mol.
[0223] According to another example, the JEFFAMINE® D series product may be JEFFAMINE® D-4000, where m is about 68 and the number average molecular weight of the polyether diamine is about 4,000 g / mol.
[0224] According to another example, A is a linear or branched and optionally substituted polyether. According to one example, the optionally substituted polyether may be based on propylene oxide (PO), ethylene oxide (EO), or a mixture of PO / EO. For example, A is an optionally substituted polyether based mainly on polyethylene glycol (PEG), and the compound of Formula 1 is the compound of Formula 5:
[0225]
[0226] Here, X1 and X2 are as defined in this specification;
[0227] R3, R4, and R5 independently and in each occurrence C1-C 10 Selected from alkyl groups;
[0228] n, o, and p are selected such that the number average molecular weight of the polyether is from about 220 g / mol to about 2,000 g / mol, including upper and lower limits;
[0229] The sum (n + p) of n and p is within the range of about 1 to about 6; and
[0230] o is within the range of about 2 to about 39.
[0231] According to one variation of the subject, the compound of Formula 1 is the compound of Formula 5 and may be a JEFFAMINE® ED series product that is the compound of Formula 5(a):
[0232]
[0233] Here, n, o, and p are selected such that the number average molecular weight of the polyether is from about 220 g / mol to about 2,000 g / mol, including upper and lower limits;
[0234] n and p are selected such that the sum (n + p) is within the range of about 1 to about 6; and
[0235] o is a number within the range of about 2 to about 39.
[0236] According to one example, the JEFFAMINE® ED series product may be JEFFAMINE® HK-511, where o is about 2, the sum (n + p) is about 1.2, and the number average molecular weight of the polyether diamine is about 220 g / mol.
[0237] According to another example, the JEFFAMINE® ED series product may be JEFFAMINE® ED-2003, where o is about 39, the sum (n + p) is about 6, and the number average molecular weight of the polyether diamine is about 2,000 g / mol.
[0238] According to another example, the JEFFAMINE® ED series product may be JEFFAMINE® ED-900, where o is about 12.5, the sum (n + p) is about 6, and the number average molecular weight of the polyether diamine is about 900 g / mol.
[0239] According to another example, the JEFFAMINE® ED series product may be JEFFAMINE® ED-600, where o is about 9, the sum (n + p) is about 3.6, and the number average molecular weight of the polyether diamine is about 600 g / mol.
[0240] According to one variant of the subject, JEFFAMINE® ED series products may be selected from the group consisting of JEFFAMINE® ED-600, ED-900 and ED-2003.
[0241] According to another example, A is linear or branched and is an arbitrarily substituted poly(C1-C 10 Alkyleneoxy)-C1-C 10 It is an alkylene, where the compound of Formula 1 can be a compound of Formula 6:
[0242]
[0243] Herein, X1 and X2 are as defined in this specification; and
[0244] q and r are numbers within the range of 1 to 10.
[0245] According to one variation of the subject, the compound of Formula 1 is a compound of Formula 6 and may be a JEFFAMINE® EDR series product of Formula 6(a):
[0246]
[0247] Here, X1, X2, q and r are as defined in this specification.
[0248] According to one example, a JEFFAMINE® EDR series product may be JEFFAMINE® EDR-148, where q and r are about 2 and the number average molecular weight of the polyether diamine is about 148 g / mol.
[0249] According to another example, the JEFFAMINE® EDR series product may be JEFFAMINE® EDR-176, where q and r are about 3 and the number average molecular weight of the polyether diamine is about 176 g / mol.
[0250] In another embodiment, A is an optionally substituted aliphatic polyester, such as polycaprolactone, and, for example, the compound of Formula 1 is the compound of Formula 7:
[0251]
[0252] Here, t and u are numbers from 1 to 10.
[0253] According to another example, a compound of Formula 1 containing at least two functional groups may be an alcohol (or polyalcohol) containing at least two hydroxyl groups, a glycol ether or diol (or glycol), a polyol such as a triol, tetraol, pentol, hexol, heptol, etc. For example, a compound containing at least two hydroxyl groups may be a linear or branched diol (or glycol), may be aliphatic or aromatic, and, for example, all diols (or glycols) are considered.
[0254] Non-limiting examples of compounds comprising at least two hydroxyl groups include glycerol (glycerin), alkanediols, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol (or propylene glycol (PG)), 1,2-butanediol, 2,3-butanediol (or dimethylene glycol), 1,3-butanediol (or butylene glycol), 1,2-pentanediol, ethohexadiol, p-methane-3,8-diol, 2-methyl-2,4-pentanediol, polycaprolactone diol, ethylene glycol (1,2-ethanediol), diethylene glycol (or ethylene diglycol), triethylene glycol, tetraethylene glycol, pentaethylene glycol, polyethylene glycol, and others It includes similar glycols and diols or combinations thereof. For example, a compound containing at least two hydroxyl groups may be selected from glycerol, diethylene glycol, ethylene glycol, propanediol, triethylene glycol, tetraethylene glycol, 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediol and polycaprolactone diol.
[0255] According to one variation of the subject, the compound containing at least two hydroxyl groups may be glycerol. According to another variation of the subject, the compound containing at least two hydroxyl groups may be diethylene glycol. According to another variation of the subject, the compound containing at least two hydroxyl groups may be 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediol.
[0256] According to other examples, a compound containing at least two functional groups may be a polyamine containing at least two amine groups, such as a diamine, a triamine, etc. For example, a compound containing at least two amine groups may be a linear or branched diamine, and may be aliphatic or aromatic, and for example, all diamines are considered. Non-limiting examples of compounds comprising at least two amine groups include propane-1,2,3-triamine, alkanediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,8-octanediamine, 1,2-propanediamine, 1,2-butanediamine, 2,3-butanediamine, 1,3-butanediamine, 1,2-pentanediamine, 2,4-diamino-2-methylpentane, ethylenediamine(1,2-diaminoethane), 1,8-diamino-3,6-dioxaoctane, 1,11-diamino-3,6,9-trioxaundecane, 4,9-dioxa-1,12-dodecanediamine, Includes 1,14-diamino-3,6,9,12-tetraoxatetradecane, poly(ethylene glycol) diamine (or PEG-diamine), JEFFAMINE® D series products (amine-terminated polypropylene glycols), JEFFAMINE® ED series products (mainly polyethylene glycol-based diamines), JEFFAMINE® EDR series products and other similar polyamines or combinations thereof.
[0257] According to one variation of the subject, a compound containing at least two amine groups has the chemical formula H2NCH2CH2(OCH2CH2) n It may be an NH2 PEG-diamine, where n is 1 or 2. According to other variations of the subject, a compound containing at least two amine groups may be a JEFFAMINE® ED series product (or O,O'-bis(2-aminopropyl) polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol). For example, JEFFAMINE® ED series products may be selected from JEFFAMINE® ED-600, ED-900, and ED-2003.
[0258] Accordingly, the present invention also relates to an ionic polymer comprising at least one repeating unit of Formula 8(a) and / or a polymer of Formula 8(b):
[0259]
[0260] Here, A is independent and linear or branched C1-C in each occurrence 10 Alkylene, linear or branched C1-C 10 Alkylene oxy C1-C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1-C 10 A substituted or unsubstituted organic group selected from alkylenes, linear or branched polyethers, and linear or branched polyesters;
[0261] X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups;
[0262] R6 is selected from hydroxyl groups, thiol groups, amine groups, and R7-X5-A-X6- groups;
[0263] R7 independently produced acrylate, methacrylate, and C1-C in each occurrence. 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonyl-C1-C 10 Alkyl-methacrylate carbonyl-C1-C 10 Alkyl-acrylate, carbonyloxy-C1-C 10 Alkyl-methacrylate, carbonyloxy-C1-C 10 Alkyl-acrylate, carbonylamino-C1-C 10 Alkyl-methacrylate and carbonylamino-C1-C 10 A crosslinkable group selected from alkyl-acrylates;
[0264] M n+ This Na + , K + , Li + , Ca 2+and Mg 2+ It is an alkali metal ion or alkaline earth metal ion selected from the group consisting of ions; and
[0265] v is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0266] According to one example, X5 and X6 can be identical. For instance, X5 and X6 are both oxygen atoms, both sulfur atoms, or both NH groups. According to one variation of the subject, X5 and X6 are both oxygen atoms. According to another variation of the subject, X5 and X6 are both NH groups.
[0267] According to another example, the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 60,000 g / mol, including upper and lower limits.
[0268] According to another example, the ionic polymer comprises at least one repeating unit of Chemical Formula 9:
[0269]
[0270] Here, M n+ , R1, R2, l, X5 and X6 are as defined in this specification; and
[0271] w is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0272] According to one example, the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 60,000 g / mol, including upper and lower limits.
[0273] According to another example, the ionic polymer comprises at least one repeating unit of Chemical Formula 10:
[0274]
[0275] Here, M n+ , m, X5 and X6 are as defined in this specification; and
[0276] x is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0277] According to one example, the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 60,000 g / mol, including upper and lower limits.
[0278] According to one variation of the object, X5 and X6 are both oxygen atoms or both NH groups, and the ionic polymer is formula 10(a) or 10(b):
[0279]
[0280] Here, M n+ , m and x are as defined in this specification.
[0281] According to another example, the ionic polymer comprises at least one repeating unit of Chemical Formula 11:
[0282]
[0283] Here, M n+ , R3, R4, R5, n, o, p X5 and X6 are as defined in this specification; and
[0284] y is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0285] According to one example, the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 60,000 g / mol, including upper and lower limits.
[0286] According to one variation of the target, X5 and X6 are both NH groups, R3, R4, and R5 are methyl groups, and the ionic polymer is chemical formula 11(a):
[0287]
[0288] Here, M n+ , n, o, p and y are as defined in this specification.
[0289] According to another example, the ionic polymer comprises at least one repeating unit of Chemical Formula 12:
[0290]
[0291] Here, M n+ , t and u are as defined in this specification; and
[0292] z is a number selected such that the number average molecular weight of the ionic polymer is approximately 8,000 g / mol to approximately 150,000 g / mol, including upper and lower limits.
[0293] According to one example, the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 60,000 g / mol, including upper and lower limits.
[0294] According to another example, an ionic polymer can be an ionic prepolymer. According to another example, an ionic polymer can be an ionic copolymer.
[0295] The present invention also relates to an ionic polymer as defined above, wherein the ionic polymer is a crosslinked ionic polymer. According to one example, the ionic polymer may further comprise at least one crosslinkable functional group. According to another example, the crosslinkable functional group may be a terminal group and may be present on at least one end of the carbon chain of the ionic polymer. According to another example, the crosslinkable functional group may be present on a side chain of the carbon chain of the ionic polymer. According to another example, the crosslinkable functional group may be present on at least one end of the carbon chain of the ionic polymer and on its side chain. For example, the crosslinkable functional group may be selected from cyanate, acrylate, and methacrylate groups. According to one variation of the subject, the crosslinkable functional group may be C1-C 10 Alkyl-acrylate group, C1-C 10 Alkyl-methacrylate group, oxycarbonylamino-C1-C 10 Alkyl-methacrylate group, oxycarbonylamino-C1-C 10 Alkyl-acrylate group, carbonylamino-C1-C 10 Alkyl-methacrylate group and carbonylamino-C1-C 10 It can be selected from alkyl-acrylate groups.
[0296] According to one example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 13:
[0297]
[0298] Here, x is as defined in this specification.
[0299] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 14:
[0300]
[0301] Here, x is as defined in this specification.
[0302] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 15:
[0303]
[0304] Here, X5, X6 and x are as defined in this specification.
[0305] According to one example, the ionic polymer may be an ionic polymer comprising at least one fragment of formula 15(a):
[0306]
[0307] Here, x is as defined in this specification.
[0308] According to another example, the ionic polymer may be an ionic polymer comprising at least one fragment of Formula 15(b):
[0309]
[0310] Here, x is as defined in this specification.
[0311] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 16:
[0312]
[0313] Here, x is as defined in this specification.
[0314] According to one example, the ionic polymer may be an ionic polymer comprising at least one fragment of Formula 16(a):
[0315]
[0316] Here, x is as defined in this specification.
[0317] According to another example, the ionic polymer may be an ionic polymer comprising at least one fragment of Formula 16(b):
[0318]
[0319] Here, x is as defined in this specification.
[0320] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 17:
[0321]
[0322] Here, X5, X6 and x are as defined in this specification.
[0323] According to one example, the ionic polymer may be an ionic polymer comprising at least one fragment of Formula 17(a):
[0324]
[0325] Here, x is as defined in this specification.
[0326] According to another example, the ionic polymer may be an ionic polymer comprising at least one fragment of Formula 17(b):
[0327]
[0328] Here, x is as defined in this specification.
[0329] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 18:
[0330]
[0331] Here, X5, X6 and x are as defined in this specification.
[0332] According to one example, the ionic polymer may be an ionic polymer comprising at least one fragment of formula 18(a):
[0333]
[0334] Here, x is as defined in this specification.
[0335] According to another example, the ionic polymer may be an ionic polymer comprising at least one fragment of formula 18(b):
[0336]
[0337] Here, x is as defined in this specification.
[0338] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 19:
[0339]
[0340] Here, w is as defined in this specification.
[0341] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Formula 20:
[0342]
[0343] Here, w is as defined in this specification.
[0344] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 21:
[0345]
[0346] Here, n, o, p and y are as defined in this specification.
[0347] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 22:
[0348]
[0349] Here, n, o, p and y are as defined in this specification.
[0350] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 23:
[0351]
[0352] Here, n, o, p and y are as defined in this specification.
[0353] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 24:
[0354]
[0355] Here, n, o, p and y are as defined in this specification.
[0356] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Formula 25:
[0357]
[0358] Here, n, o, p and y are as defined in this specification.
[0359] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 26:
[0360]
[0361] Here, w and x are as defined in this specification.
[0362] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 27:
[0363]
[0364] Here, w and x are as defined in this specification.
[0365] According to another example of the subject, the ionic polymer may be an ionic polymer comprising at least one fragment of Chemical Formula 28:
[0366]
[0367] Here, w and x are as defined in this specification.
[0368] The present technology also relates to a polymer composition comprising an ionic polymer as defined above.
[0369] According to one example, the polymer composition or ionic polymer may optionally further comprise at least one additional component or additive, such as an ionic conductor, inorganic particles, glass particles, ceramic particles (e.g., nanoceramics), salts, and other similar additives or combinations thereof. For example, the additional component or additive may be a filler additive and may comprise metal oxide particles or metal nanoparticles. For example, the filler additive may comprise particles or nanoparticles of titanium dioxide (TiO2), alumina (Al2O3), and / or silicon dioxide (SiO2).
[0370] The present invention also relates to a method for preparing an ionic polymer or a polymer composition as defined herein, and the method comprises the following steps:
[0371] (i) a step of preparing a metal bis(halosulfonyl)imide of Formula 2; and
[0372] (ii) a step of reacting at least one compound of Formula 1, comprising at least two functional groups as described above, with the metal bis(halosulfonyl)imide of Formula 2.
[0373] According to one example, the method further comprises the step of preparing bis(halosulfonyl)imide. For example, the step of preparing bis(halosulfonyl)imide may be carried out by reacting a sulfamic acid (H3NSO3) with a halosulfonic acid of the formula HSO3X3 (where X3 is as defined above) in the presence of at least one halogenating agent. For example, the preparation of bis(halosulfonyl)imide may be carried out by a method as described by Beran et al., and may be as illustrated in Reaction Scheme 1 below (Beran et al. , Zeitschrift fur anorganische and allgemeine Chemie 631.1 (2005): 55-59):
[0374]
[0375] Here, X3 and X4 are as defined above.
[0376] According to one variant of the target, bis(halosulfonyl)imide is bis(chlorosulfonyl)imide (HN(SO2Cl)2).
[0377] According to one example, bis(chlorosulfonyl)imide can be prepared by the reaction of sulfamic acid and chlorosulfonic acid (HSO3Cl) in the presence of at least one halogenating agent.
[0378] According to another example, the step of preparing bis(halosulfonyl)imide may further include a purification step. For example, the purification step may be carried out by any known compatible purification method. For example, the purification step may be carried out by distillation.
[0379] According to another example, the halogenating agent may be selected from any known compatible halogenating agents. For example, the halogenating agent may also act as a reaction medium and / or solvent and may be selected for ease of isolation during an optional subsequent purification step. For example, the halogenating agent may be selected from phosphorus trichloride (PCl3), phosphorus pentachloride (PCl5), thionyl chloride (SOCl2), thionyl fluoride (SOF2), phosphorus oxychloride (POCl3), and oxalyl chloride ((COCl)2). For example, the halogenating agent is a chloride. According to one variation of the subject, the halogenating agent is thionyl chloride.
[0380] Without wishing to be bound by theory, thionyl chloride can, for example, react with an amino group to form a (-N=S=O) group. Therefore, for example, the reaction mechanism between sulfamic acid and chlorosulfonic acid in the presence of thionyl chloride may be as illustrated in Reaction Scheme 2:
[0381]
[0382] For example, in the presence of 2 equivalents of thionyl chloride, 1 equivalent of sulfamic acid reacts with 1 equivalent of chlorosulfonic acid to form bis(chlorosulfonyl)imide.
[0383] According to another example, a halogenating agent (e.g., thionyl chloride) may be added in excess. For example, the amount of the halogenating agent may be within the range of about 2 equivalents to about 5 equivalents relative to the sulfamic acid, including upper and lower limits. For example, the amount of the halogenating agent may be within the range of about 2 equivalents to about 4 equivalents or about 2 equivalents to about 3 equivalents or about 2 equivalents to about 2.75 equivalents or about 2 equivalents to about 2.5 equivalents per sulfamic acid equivalent, including upper and lower limits. According to one variation of the subject, the amount of the halogenating agent is about 2.75 equivalents relative to the sulfamic acid.
[0384] According to another example, the reaction between a sulfamic acid and a halosulfonic acid in the presence of at least one halogenating agent is carried out at a sufficiently high temperature for a sufficient amount of time to allow for a substantially complete reaction. For example, the reaction between a sulfamic acid and a halosulfonic acid in the presence of at least one halogenating agent is carried out at a temperature within the range of about 60°C to about 150°C, including upper and lower limits. For example, the step of preparing bis(halosulfonyl)imide may be carried out at a temperature within the range of about 70°C to about 145°C, or about 80°C to about 140°C, or about 90°C to about 100°C, or about 110°C to about 140°C, or about 120°C to about 140°C, or about 125°C to about 140°C, or about 125°C to about 135°C, including upper and lower limits. According to one variation of the target, the step of preparing bis(halosulfonyl)imide can be carried out at a temperature of about 130°C for, for example, about 24 hours.
[0385] According to another example, a metal bis(halosulfonyl)imide is prepared by a metallization reaction of bis(halosulfonyl)imide. For example, the step of preparing the metal bis(halosulfonyl)imide or the metallization step may be carried out by a reaction between the bis(halosulfonyl)imide and at least one metallizing agent in the presence of a solvent. For example, the step of preparing the metal bis(halosulfonyl)imide or the metallization step may be carried out by a method as illustrated in Reaction Scheme 3:
[0386]
[0387] Here, X3, X4 and M n+ They are as defined above.
[0388] According to another example, the metallizer may be selected from all known compatible metallizers. According to one variation of the subject, the metal of the metallizer is an alkali metal or alkaline earth metal selected from lithium, sodium, potassium, calcium, and magnesium. For example, the metal of the metallizer is an alkali metal selected from lithium, sodium, and potassium. According to another variation of the subject, the alkali metal is lithium, the metallizer is the lithiating agent, and the metallization step is the lithiation step. For example, the lithiating agent may be selected for its ability to readily deprotonate and lithiate bis(halosulfonyl)imide, for example, bis(chlorosulfonyl)imide. According to one variation of the subject, lithium bis(halosulfonyl)imide is Paul et al. et al. , Journal of Inorganic and Nuclear Chemistry It can be manufactured by the method as described in 39.3 (1977): 441-442).
[0389] Non-limiting examples of lithiating agents include lithium hydroxide (LiOH), lithium carbonate (Li2CO3), lithium hydrogen bicarbonate (LiHCO3), lithium hydride (LiH), metallic lithium, lithium chloride (LiCl), lithium bromide (LiBr), lithium iodide, and the chemical formula RCO2Li (where R is a linear or branched C1-C 10 It includes lithium carboxylates and lithium oxalates (C2Li2O4) of which are alkyl groups or aromatic hydrocarbons. According to one variation of the subject, the lithiating agent is lithium chloride.
[0390] According to another example, the solvent used in the step of preparing the metal bis(halosulfonyl)imide or in the metallization step may be an organic solvent, for example, a polar aprotic solvent. For example, the solvent may be selected from the group consisting of N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), tetrachloromethane, chloroform, acetonitrile, tetrahydrofuran (THF), and miscible combinations of at least two of these. According to one variation of the subject, the solvent for the metallization reaction is N,N-dimethylformamide. For example, the solvent may also act as an activator for the subsequent polymerization reaction. According to one example, N,N-dimethylformamide can substantially improve the yield of a step in which at least one compound of Formula 1 as described above is reacted with a metal bis(halosulfonyl)imide as defined herein by forming a complex with a metal bis(halosulfonyl)imide. For example, the complex is [formulated in] Higashi et al. (Higashi et al. , Journal of Polymer Science It may be a complex as described by : Polymer Chemistry Edition 22, No. 7 (1984): 1653-1660).
[0391] According to another example, the metallizing agent may be added to the bis(halosulfonyl)imide:metallizing agent in a molar ratio of 1:1. Alternatively, the metallizing agent may be added in excess of the bis(halosulfonyl)imide. For example, the amount of the metallizing agent may be within the range of about 1 equivalent to about 5 equivalents per bis(halosulfonyl)imide equivalent, including upper and lower limits. For example, the amount of the metallizing agent may be within the range of about 1 equivalent to about 4 equivalents or about 1 equivalent to about 3 equivalents or about 1 equivalent to about 1.5 equivalents or about 1 equivalent to about 1.3 equivalents or about 1 equivalent to about 1.2 equivalents per bis(halosulfonyl)imide equivalent, including upper and lower limits. According to one variation of the subject, the amount of metallizing agent may be within the range of about 1 equivalent to about 1.5 equivalents per bis(halosulfonyl)imide equivalent, including upper and lower limits.
[0392] According to another example, the step of preparing a metal bis(halosulfonyl)imide or the metallization step may be carried out at a temperature within a range of about 20°C to about 150°C, including upper and lower limits. For example, the step of preparing a metal bis(halosulfonyl)imide or the metallization step may be carried out at a temperature within a range of about 30°C to about 135°C, or about 40°C to about 130°C, or about 50°C to about 125°C, or about 60°C to about 120°C, or about 70°C to about 115°C, or about 80°C to about 110°C, or about 90°C to about 105°C, including upper and lower limits. According to one variation of the object, the step of preparing a metal bis(halosulfonyl)imide or the metallization step may be carried out at a temperature of about 100°C.
[0393] According to another example, the step of preparing the metal bis(halosulfonyl)imide or the metallization step can be carried out at a sufficiently high temperature for a sufficient amount of time to allow for a substantially complete metallization reaction.
[0394] For example, the metallization reaction may be carried out for a period of time within the range of about 10 hours to about 48 hours, or about 10 hours to about 24 hours, or about 12 hours to about 24 hours, including upper and lower limits. According to one variation of the object, the metallization reaction may be carried out for a period of time within the range of about 12 hours to about 24 hours.
[0395] According to another example, the step of reacting at least one compound of Formula 1 comprising at least two functional groups as described above with a metal bis(halosulfonyl)imide of Formula 2 as defined herein is a polymerization step. For example, any compatible polymerization methods are considered. According to one variation of the subject, the polymerization of the metal bis(halosulfonyl)imide of Formula 2 and at least one compound of Formula 1 may be carried out by polycondensation or by polyesterization, for example, by a Fischer-Speier esterification reaction or a modified Steglich esterification. For example, the polycondensation may be thermal polycondensation. According to one variation of the subject, the polycondensation may be Slavko et al. et al. , Chemical Science It can be executed by the method as described in 8.10 (2017): 7106-7111).
[0396] According to another example, the reaction between at least one compound of Formula 1 as described above and the metal bis(halosulfonyl)imide of Formula 2 can be carried out in the presence of a solvent, for example, an organic solvent. For example, the solvent may be selected from the group consisting of N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethylacetamide, tetrachloromethane, chloroform, acetonitrile, tetrahydrofuran, and miscible combinations of at least two of these. According to one variation of the subject, the solvent for the polymerization reaction is N,N-dimethylformamide. For example, the solvent may also act as an activator in the polymerization reaction.
[0397] According to another example, polymerization may be carried out in the presence of at least one polymerization catalyst and at least one co-catalyst and / or at least one acylation catalyst, optionally. According to another example, polymerization may also be carried out in the presence of a base and without a polymerization catalyst. For example, any compatible polymerization catalyst, co-catalyst, acylation catalyst, and base are considered. According to one example, the polymerization catalyst may be an acid catalyst (e.g., a Lewis acid catalyst). For example, the polymerization catalyst is Slavko et al. (Slavko et al. , Chemical ScienceIt may be a boron-based catalyst, a boric acid-based catalyst, a boronic acid-based catalyst, or a boric acid-based catalyst as described in 8.10 (2017): 7106-7111). Non-limiting examples of boron-based polymerization catalysts include diarylboric acids of the formula Ar2BOH (where Ar is an aryl group), diphenylboric acid, phenylboronic acid, trifluorophenylboronic acid, 9H-9-bora-10-thianthracen-9-ol, 10H-phenoxaborinine-10-ol, boron tribromide (BBr3), boron trichloride (BCl3), acyl fluoroborate, triethyloxonium fluoroborate, boron trifluoride etherate, boron trifluoride (BF3), tris(pentafluorophenyl)borane, and other similar boron-derived catalysts, or combinations of at least two of these where compatible.
[0398] According to another example, the polymerization catalyst can be a nucleophilic catalyst. For example, polymerization can be catalyzed by bases such as pyridine, 4-dimethylaminopyridine (DMAP), and pyridine derivatives.
[0399] According to another example, polymerization can be carried out in the presence of bases such as triethylamine (Et3N), N,N-diisopropylethylamine (iPr2NEt), pyridine, and pyridine derivatives. According to one variation of the subject, the base is triethylamine. For example, the base can be used to deprotonate the catalyst or to regenerate the catalyst. The base can also be used to neutralize the acid (e.g., hydrochloric acid (HCl)) released during the reaction.
[0400] According to one variation of the object, polymerization may be carried out in the presence of triethylamine, diphenylborinic acid or trifluorophenylborinic acid, N,N-dimethylformamide, and 4-dimethylaminopyridine. According to another variation of the object, polymerization may be carried out in the presence of triethylamine, diphenylborinic acid or trifluorophenylborinic acid, and N,N-dimethylformamide. Alternatively, polymerization may be carried out in the presence of N,N-dimethylformamide and optionally a base without the addition of a catalyst, a co-catalyst, and / or an acylation catalyst.
[0401] According to another example, polymerization can be carried out by the method as illustrated in Reaction Scheme 4:
[0402]
[0403] Here, X1, X2, X3, X4, X5, X6, M n+ , A and v are as defined above.
[0404] According to another example, the method further comprises a post-functionalization or post-polymerization modification step. For example, the post-functionalization of the ionic polymer is performed in anticipation of crosslinking of the ionic polymer. Thus, the post-functionalization step of the ionic polymer may be optionally performed to functionalize the ionic polymer by introducing at least one functional group as defined above, e.g., a crosslinkable functional group. The crosslinkable functional group may be present on at least one end of the carbon chain of the ionic polymer and / or on its side chain. For example, at least one terminal group or substituent (e.g., R1 and / or R2) of the carbon chain of the ionic polymer contains functionality that allows crosslinking of the ionic polymer. In some cases, the presence of such functional groups may contribute to the control of the properties of the ionic polymer.
[0405] An optional post-functionalization or post-polymerization modification step may be carried out by a reaction between at least one functional group of the ionic polymer and at least one precursor of a crosslinkable functional group. For example, the crosslinkable functional group may be acrylate, methacrylate, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-acrylate, aminocarbonyl-C1-C 10 Alkyl-methacrylate, aminocarbonyl-C1-C 10 Alkyl-acrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylate, oxycarbonylamino-C1-C 10 Alkyl-acrylate, carbonyloxy-C1-C 10 Alkyl-methacrylate, carbonyloxy-C1-C 10 Alkyl-acrylate, carbonylamino-C1-C 10 Alkyl-methacrylate and carbonylamino-C1-C 10 It is selected from alkyl-acrylates.
[0406] According to other examples, the post-functionalization reaction may be selected from esterification and amidation reactions. For example, the post-functionalization reaction may be Fisher esterification, Steglich esterification, or a reaction as described in U.S. Patent No. 7,897,674 B2 (Zaghib et al.). According to other examples, an ionic polymer having a carbamate functional group may be obtained by a reaction between 2-isocyanatoethyl methacrylate and the functional group of the ionic polymer. According to other examples, an ionic polymer having an acrylate functional group may be obtained by a reaction between the functional group of the ionic polymer and acrylic acid (CH2=CHCOOH), methacrylic acid (CH2C(CH3)COOH), acryloyl chloride (CH2=CHCO(Cl)), methacryloyl chloride (CH2=C(CH3)CO(Cl)), or other compatible carboxylic acid derivatives.
[0407] According to another example, the method further comprises a step of substituting at least one halogen atom, e.g., a chlorine atom. For example, the substitution step may be carried out by a nucleophilic substitution reaction between the halogen atom and a nucleophilic reagent. According to one example, the nucleophilic reagent may be a salt, e.g., a lithium salt such as lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or a silver salt such as silver tetrafluoroborate (AgBF4). According to one variation of the subject, the substitution step may be carried out by nucleophilic substitution of at least one chlorine atom to an anion (e.g., TFSI or BF4). According to one example, the ionic polymer is brought into contact with at least one nucleophilic reagent. For example, the ionic polymer may be brought into contact with a sufficient amount of nucleophilic reagent for a sufficient amount of time at a sufficiently high temperature to ensure a substantially complete nucleophilic substitution reaction. For example, the ionic polymer can be contacted with about 10 wt% of LiTFSI at a temperature of about 40°C for about 2 hours to ensure a substantially complete nucleophilic substitution reaction. For example, the nucleophilic reagent can be subsequently removed by filtration and precipitation in a suitable solvent, for example, ethyl acetate or methanol.
[0408] According to another example, the method further comprises a separation or purification step. The separation or purification step may be carried out by any known compatible separation or purification method. For example, the separation or purification step may be carried out by a separation method based on molecular weight. The separation or purification method may be carried out by liquid chromatography (e.g., stereoexclusion chromatography) or filtration (e.g., membrane filtration or separation method). For example, the separation or purification method is carried out by membrane filtration (e.g., nanofiltration or ultrafiltration). In some embodiments, the separation or purification step may be carried out by ultrafiltration. For example, ultrafiltration is carried out at 1,000 DA (Dalton) (or 1.66 x 10⁻¹⁰) to separate low molecular weight impurities (e.g., less than 1,000 DA) from an ionic polymer. -15 It can be implemented with a membrane having a molecular weight cutoff (MWCO) limit of μg. According to other examples, the separation or purification step can be performed before and / or after the post-functionalization or post-polymerization modification step.
[0409] According to another example, the method further comprises the step of coating (also referred to as spreading) a polymer composition or suspension containing an ionic polymer as described above. For example, the coating step may be performed by at least one of a printing method such as doctor blade coating, comma coating, reverse comma coating, gravure coating, or slot-die coating. According to one variation of the subject, the coating step is performed by a doctor blade coating or a slot-die coating. According to one example, the polymer composition or suspension containing an ionic polymer may be coated onto a substrate or support (e.g., a substrate made of silicone resin, polypropylene, or silicone-treated polypropylene). For example, the substrate or support film may be subsequently removed. According to another example, the polymer composition or suspension containing an ionic polymer may be coated directly onto an electrode.
[0410] According to another example, the method further comprises a step of drying the polymer composition or ionic polymer as defined above. According to one example, the drying step may be performed to remove any residual solvent. According to another example, the drying step and the coating step may be performed simultaneously and / or separately.
[0411] According to another example, the method further comprises the step of crosslinking a polymer composition or an ionic polymer as defined above. For example, at least one terminal group or substituent (e.g., R1 and / or R2) of the ionic polymer comprises at least one functional group that enables crosslinking of the ionic polymer. According to another example, the crosslinking step may be carried out by UV irradiation, by heat treatment, by microwave irradiation, under an electron beam, by gamma irradiation, or by X-ray irradiation. According to one variation of the object, the crosslinking step is carried out by UV irradiation. According to another variation of the object, the crosslinking step is carried out by heat treatment. According to another variation of the object, the crosslinking step is carried out under an electron beam. According to another example, the crosslinking step may be carried out in the presence of a crosslinking agent, a thermal initiator, a photoinitiator, a catalyst, a plasticizer, or a combination of at least two of these. For example, the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone (Irgacure™ 651). For example, the polymer composition and the ionic polymer can be solidified after crosslinking.
[0412] The present technology also relates to the use of polymer compositions or ionic polymers as defined above in electrochemical applications.
[0413] According to one example, the polymer composition or ionic polymer may be used in electrochemical cells, batteries, and supercapacitors (e.g., carbon-carbon supercapacitors, hybrid supercapacitors, etc.). According to another example, the polymer composition or ionic polymer may be used in electrochromic materials, electrochromic cells, electrochromic devices (ECDs), and electrochromic sensors as described in U.S. Patent No. 5,356,553.
[0414] According to another example, the polymer composition as defined herein may be a solid polymer electrolyte composition. According to another example, the polymer composition as defined herein may be used as a component of an electrode material, for example, as a binder in an electrode material.
[0415] Accordingly, the present invention also relates to a solid polymer electrolyte comprising an ionic polymer as defined above or a polymer composition as defined above (i.e., comprising an ionic polymer as defined above), wherein the ionic polymer may be optionally crosslinked if crosslinkable functional groups are present within the ionic polymer.
[0416] According to one example, the solid polymer electrolyte composition or solid polymer electrolyte as defined above may further comprise at least one salt. For example, the salt may be dissolved in the solid polymer electrolyte composition or in the solid polymer electrolyte.
[0417] The salt can be an ionic salt, such as a lithium salt, sodium salt, potassium salt, calcium salt, or magnesium salt. According to one variation of the subject, the ionic salt is a lithium salt. Non-limiting examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanomidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3)(LiTf), and lithium fluoroalkyl phosphate. Li[PF3(CF2CF3)3](LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4](LiTFAB), lithium bis(1,2-benzenediolatto(2-)-O,O')borate Li[B(C6O2)2](LiBBB), and combinations of at least two of these. According to one variation of the subject, the lithium salt may be LiPF6. According to another variation of the subject, the lithium salt may be LiFSI. According to another variation of the subject, the lithium salt may be LiTFSI. Non-limiting examples of sodium salts include the salts described above in which the lithium ion is replaced by a sodium ion. Non-limiting examples of potassium salts include the salts described above in which the lithium ion is replaced by a potassium ion. Non-limiting examples of calcium salts include the salts described above in which the lithium ion is replaced by a calcium ion and the number of anions present in the salt is adjusted to the charge of the calcium ion.Non-limiting examples of magnesium salts include the salts described above in which lithium ions are replaced by magnesium ions and the number of anions present in the salt is adjusted to the charge of magnesium ions.
[0418] According to another example, the solid polymer electrolyte composition or solid polymer electrolyte as defined above may additionally optionally include additional components or additives such as ion-conducting materials, inorganic particles, glass particles, ceramic particles (e.g., nanoceramics), other similar additives, or a combination of at least two of these. For example, additional components or additives may be selected for their high ion conductivity and, in particular, may be added to improve the conductivity of lithium ions. According to one variation of the subject, additional components or additives may be selected from NASICON, LISICON, thio-LiSICON, crystalline and / or amorphous garnets, and a combination of at least two of these.
[0419] According to another example, the solid polymer electrolyte may be in the form of a thin film. For example, the film comprises at least one electrolyte layer containing the solid polymer electrolyte. In some cases, additional components or additives defined above may be included in the electrolyte layer or, for example, in a separate ion-conducting layer deposited on the electrolyte layer, and / or substantially dispersed therein.
[0420] The present invention also relates to an electrode material comprising at least one electrochemically active material and an ionic polymer as defined above or a polymer composition as defined herein (i.e., comprising an ionic polymer as defined herein). In one example, the ionic polymer acts as a binder in the electrode material. In one example, the electrode material is an anode material. In another example, the electrode material is a cathode material.
[0421] According to one example, electrochemically active materials may be in the form of particles. Non-limiting examples of electrochemically active materials include metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, titanates, and lithium titanates.
[0422] For example, the metal of the electrochemically active material may be selected from the following elements: titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), chromium (Cr), copper (Cu), antimony (Sb), and, if compatible, a combination of at least two of these. According to one variation of the object, the metal of the electrochemically active material may be selected from titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), and, if compatible, a combination of at least two of these.
[0423] Non-limiting examples of electrochemically active materials are also titanates and lithium titanates (e.g. , TiO2, Li2TiO3, Li4Ti5O 12 , H2Ti5O 11 , H2Ti4O9 and combinations thereof), metal phosphates and lithiated metal phosphates (e.g., LiM'PO4 and M'PO4, where M' can be Fe, Ni, Mn, Mg, Co and combinations thereof), vanadium oxide and lithium vanadium oxide (e.g. ,LiV3O8, V2O5, LiV2O5, etc.) and other lithium metal oxides with the chemical formulas LiMn2O4, LiM''O2 (where M'' is selected from Mn, Co, Ni and combinations thereof), Li(NiM''')O2 (where M''' is selected from Mn, Co, Al, Fe, Cr, Ti, Zr, other similar metals and combinations thereof), and if compatible, at least two combinations of these are included.
[0424] According to another example, an electrochemically active material may be optionally doped with other elements or impurities, and these elements or impurities may be included in small amounts to, for example, control or optimize the electrochemical properties of the electrochemically active material. For example, an electrochemically active material may be doped by partial substitution of metals with other ions. For example, an electrochemically active material may be doped with transition metals (e.g., Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, or Y) and / or metals other than transition metals (e.g., Mg, Al, or Sb).
[0425] According to another example, the electrochemically active material may be in the form of particles (e.g., microparticles and / or nanoparticles) that may be newly formed or commercially available and may additionally contain a coating material. The coating material may be an electrically conductive material, for example, the coating may be a carbon coating.
[0426] According to another example, the electrode material is a cathode material comprising, for example, carbon-coated lithium titanate (c-LTO) as an electrochemically active material.
[0427] According to another example, the electrode material may also optionally include additional components or additives such as ion conductors, inorganic particles, glass or ceramic particles, nanoceramics (e.g., Al2O3, TiO2, SiO2 and other similar compounds), salts (e.g., lithium salts) and other similar additives. For example, the additional components or additives may be ion conductors selected from NASICON, LISICON, thio-LiSICON, crystalline and / or amorphous garnet, sulfides, sulfur halides, phosphates and thio-phosphate compounds, and combinations of at least two of these.
[0428] According to other examples, the electrode material as defined herein may further comprise an electrically conductive material. Non-limiting examples of electrically conductive materials include carbon black (e.g., Ketjen™ carbon and Super P™ carbon), acetylene black (e.g., Shawinigan carbon and Denka™ carbon black), graphite, graphene, carbon fiber (e.g., vapor-grown carbon fiber (VGCF)), carbon nanofiber, carbon nanotube, and combinations of at least two of these.
[0429] The present invention also relates to an electrode comprising an electrode material as defined herein on a current collector (e.g., aluminum or copper). Alternatively, the electrode may be a self-supported electrode. According to one variation of the subject, the electrode as defined herein is an anode. According to another variation of the subject, the electrode as defined herein is a cathode.
[0430] The present invention also relates to an electrochemical cell comprising a cathode, an anode, and an electrolyte, wherein at least one of the cathode, the anode, and the electrolyte comprises an ionic polymer as defined herein or a polymer composition as defined herein.
[0431] The present invention also relates to an electrochemical cell comprising a cathode, an anode, and an electrolyte, wherein at least one of the cathode, the anode, and the electrolyte is as defined herein. According to one variation of the object, the electrolyte is a solid polymer electrolyte as defined herein. According to another embodiment of the object, the cathode is as defined herein. According to another variation of the object, the anode is as defined herein. According to one variation of the object, the electrolyte is a solid polymer electrolyte as defined herein and the anode is as defined herein.
[0432] The present invention also relates to a battery comprising at least one electrochemical cell as defined herein. For example, the battery may be selected from a lithium battery, a lithium-ion battery, a lithium-sulfur battery, a sodium battery, a sodium-ion battery, a magnesium battery, and a magnesium-ion battery. According to one variation of the subject, the battery is a lithium battery or a lithium-ion battery. For example, the battery may be an all-solid-state battery (e.g., an all-solid-state lithium battery).
[0433] Examples
[0434] The following embodiments are for illustrative purposes only and should not be construed as further limiting the scope of the invention as considered. These embodiments will be better understood by referring to the accompanying drawings.
[0435] Example 1 - Bis(chlorosulfonyl)imide (Cl-SO 2 -NH-SO 2 Synthesis of -Cl)
[0436] The synthesis of bis(chlorosulfonyl)imide was carried out by reacting sulfamic acid with thionyl chloride, and subsequently by reacting the resulting product with chlorosulfonic acid. Thus, bis(chlorosulfonyl)imide was prepared by the method as shown in Reaction Scheme 5:
[0437]
[0438] 1.0 equivalent of sulfamic acid was placed in a clean, dry flask equipped with a magnetic bar and suspended in an excess volume of thionyl chloride (2.75 equivalents). All operations were carried out under a constant flow of nitrogen. 1.0 equivalent of chlorosulfonic acid was added dropwise, and a vapor trap containing a saturated aqueous sodium hydroxide solution or a saturated aqueous lithium hydroxide solution to neutralize hydrochloric acid vapor was fitted to the flask. Subsequently, the resulting mixture was heated in a sand bath at about 130°C under constant stirring for about 24 hours.
[0439] The mixture was subsequently purified by vacuum distillation at a temperature of approximately 180°C, and the mixture was heated using a heat gun. Distillation was carried out in a refrigerant equipped with a cold trap filled with liquid nitrogen without water circulation. At the end of the distillation, the temperature was increased to ensure that the distillation was complete. To prevent contamination of the product, the distillation was stopped before smoke began to form.
[0440] The product obtained accordingly was cooled to form bis(chlorosulfonyl)imide crystals and stored in a refrigerator.
[0441] Example 2 - Synthesis of Lithium Bis(Chlorosulfonyl)imide
[0442] Lithium bis(chlorosulfonyl)imide was prepared by the method as shown in Reaction Scheme 6:
[0443]
[0444] The synthesis of lithium bis(chlorosulfonyl)imide was carried out in a glove box under an inert nitrogen atmosphere. 1.0 equivalent of the bis(chlorosulfonyl)imide prepared in Example 1 was weighed and introduced into a flask that had been previously cleaned and dried at 120°C for 2 hours to remove any residual water. The flask was then sealed with a stopper. About 1.0 to about 1.5 equivalents of lithium chloride dissolved in anhydrous N,N-dimethylformamide were added to the flask through the stopper using a needle.
[0445] Next, the flask was removed from the glove box and placed at a temperature of about 100°C for about 24 hours under a constant flow of nitrogen to ensure complete lithiation of the mixture and activation of lithium bis(chlorosulfonyl)imide by N,N-dimethylformamide.
[0446] Example 3 - Polymerization
[0447] (a) Polymerization of diethylene glycol and lithium bis(chlorosulfonyl)imide prepared in Example 2 (Polymer 1)
[0448] Polymerization was carried out by catalyst-controlled polycondensation of diethylene glycol and lithium bis(chlorosulfonyl)amide prepared in Example 2. Thus, the polymerization was controlled by a polycondensation catalyst.
[0449] The mixture containing lithium bis(chlorosulfonyl)imide prepared in Example 2 was cooled in an ice bath for 20 minutes. The stopper was subsequently removed, and the neck of the flask was subsequently washed with a solvent to recover as much of the product as possible. The flask was subsequently sealed with a new stopper.
[0450] Next, 3 equivalents of triethylamine were added to the mixture. Subsequently, 25 mg of trifluorophenylboronic acid and 400 mg of 4-dimethylaminopyridine were added to the mixture. Next, 1 equivalent of diethylene glycol was added, and the reaction mixture was heated at a temperature of about 100°C for about 72 hours.
[0451] The reaction mixture was continuously cooled, filtered, and precipitated in ethyl acetate. The reaction mixture was placed in an ice bath for about 30 minutes and subsequently drained.
[0452] The resulting polymer was subsequently dissolved in a solvent mixture of isopropanol and acetone (2:8 volume ratio) and placed in a refrigerator for about 1 hour. The mixture was then filtered to remove residual triethylamine chloride. The solvent was then evaporated using a rotary evaporator at a temperature of about 60°C. Finally, the polymer was dried in a vacuum oven at a temperature of about 60°C.
[0453] Accordingly, the obtained polymer 1 was dissolved in 400 ml of water and filtered for about 7 hours by ultrafiltration through a membrane having a molecular weight cutoff limit of 1,000 DA.
[0454] The substitution of chlorine atoms was carried out by a nucleophilic substitution reaction using silver tetrafluoroborate as a nucleophilic reagent. The required amount of silver tetrafluoroborate was calculated by determining the chloride ions present in Polymer 1 using Mohr's method. Subsequently, the required amount of silver tetrafluoroborate was dissolved in a minimum amount of water and added to a solution containing 1 g of Polymer 1 dissolved in 20 ml of water. The solution was then stirred at room temperature for approximately 15 minutes, followed by filtration and washing with methanol. The resulting filtrate was then evaporated until dry. The substitution was confirmed by fluorine nuclear magnetic resonance (fluorine-19 NMR).
[0455] (b) Post-functionalization of the polymer prepared in Example 3(a) (Polymer 2)
[0456] Polymer 2 was prepared by post-functionalization of Polymer 1 provided in Example 3(a) to introduce crosslinkable groups.
[0457] 4 g of the polymer prepared in Example 3(a) was dissolved in 25 ml of anhydrous N,N-dimethylformamide. Subsequently, 1 ml of 2-isocyanatoethyl acrylate was added to the solution, and the resulting mixture was heated at a temperature of about 50°C under a nitrogen atmosphere for about 5 to 12 hours. Subsequently, 5 ml of methanol was added to the solution, and the solution was cooled to room temperature.
[0458] Accordingly, the obtained polymer (polymer 2) was dissolved in 400 ml of water and filtered for about 7 hours by ultrafiltration through a membrane having a molecular weight cutoff limit of 1,000 DA.
[0459] Polymer 2 was analyzed by stereoexclusion chromatography (SEC), proton nuclear magnetic resonance (proton NMR), Fourier transform infrared spectroscopy (FTIR), and differential scanning calorimetry (DSC).
[0460] Figure 1 shows the results of stereoexclusion chromatography analysis obtained for Polymer 2. Based on these results, the average molecular weight of Polymer 2 was determined (g / mol). Using a refractive index (RI) detector and 0.90 mL·min -1 Stereoexclusion chromatography was performed at the flow rate. The stereoexclusion chromatography results obtained for polymer 2 are provided in Tables 1 and 2.
[0461]
[0462]
[0463] Figure 2 shows the proton NMR spectrum obtained for polymer 2. Figure 3 shows the results of differential scanning calorimetry obtained for polymer 2. As shown in Figure 3, polymer 2 has a glass transition temperature (T g ) = -53℃.
[0464] The lithium concentration of Polymer 2 was subsequently determined. Subsequently, 30 wt% of a modified ion exchange resin commercially available under the trade name DOWEX® was added to the solution. The resulting suspension was stirred at room temperature for approximately 12 hours and subsequently filtered. The resulting filtrate was evaporated until dry and dried in a vacuum oven at a temperature of approximately 65°C for approximately 24 hours. Lithium nuclear magnetic resonance for a standard solution of lithium chloride ( 7 The lithium concentration in the polymer was determined by Li NMR.
[0465] The above modified ion exchange resin was obtained by the following method: a glass column using Dowex® 50WX8 (H + ) It was packed with 30 g of resin and moistened with a 2 M aqueous lithium hydroxide solution. The resin was washed at the end of the column until a basic pH was reached. Subsequently, the modified resin was washed with ultrapure water until a neutral pH was reached, followed by washing with 300 ml of methanol. The resin was then oven-dried at approximately 60°C for about 12 hours. Alternatively, Dowex® 50WX8 (H + A modified ion exchange resin can be prepared by stirring 30 g of resin in 300 ml of a 2 M aqueous lithium hydroxide solution for about 12 hours and then filtering the resulting suspension. The modified resin was then washed and dried as described above.
[0466] (c) Polymerization of 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediol and lithium bis(chlorosulfonyl)imide prepared in Example 2 (Polymer 3)
[0467] Polymerization was carried out by catalyst-controlled polycondensation of 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediol and lithium bis(chlorosulfonyl)imide prepared in Example 2.
[0468] The mixture containing lithium bis(chlorosulfonyl)imide of Example 2 was cooled in an ice bath for 20 minutes. The stopper was subsequently removed, and the neck of the flask was washed with a solvent to recover as much of the product as possible. The flask was subsequently sealed with a new stopper.
[0469] Next, 3 equivalents of triethylamine were added to the mixture. Subsequently, 25 mg of trifluorophenylboronic acid and 400 mg of 4-dimethylaminopyridine were added to the mixture. Next, 1 equivalent of 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediol was added, and the reaction mixture was heated at a temperature of about 100°C for about 72 hours.
[0470] The reaction mixture was continuously cooled, filtered, and precipitated in ethyl acetate. The reaction mixture was placed in an ice bath for about 30 minutes and continuously drained.
[0471] The polymer was subsequently dissolved in a solvent mixture (2:8 volume ratio) containing isopropanol and acetone and placed in a refrigerator for about 1 hour. The mixture was then filtered to remove residual triethylamine chloride. The solvent was subsequently evaporated using a rotary evaporator at a temperature of about 60°C. Finally, the polymer was dried in a vacuum oven at a temperature of about 60°C.
[0472] Accordingly, the obtained polymer (polymer 3) was dissolved in 400 ml of water and filtered for about 7 hours by ultrafiltration through a membrane having a molecular weight cutoff limit of 1,000 DA.
[0473] Substitution of chlorine atoms was subsequently carried out by the method described in Example 3(a).
[0474] (d) Post-functionalization of the polymer prepared in Example 3(c) (polymer 4)
[0475] Polymer 4 was prepared by post-functionalization of Polymer 3 provided in Example 3(c) to introduce crosslinkable groups.
[0476] 4 g of the polymer prepared in Example 3(c) was dissolved in 25 ml of anhydrous N,N-dimethylformamide. Then, 1 ml of 2-isocyanatoethyl methacrylate was added to the solution, and the resulting mixture was heated at a temperature of about 50°C under a nitrogen atmosphere for about 5 to 12 hours.
[0477] Accordingly, the obtained polymer (polymer 4) was dissolved in 400 ml of water and filtered for about 7 hours by ultrafiltration through a membrane having a molecular weight cutoff limit of 1,000 DA.
[0478] Polymer 4 was analyzed by stereoexclusion chromatography, and the results are shown in Fig. 4. Using a refractive index detector and 0.80 mL·min -1 Stereoexclusion chromatography was performed at the flow rate. The stereoexclusion chromatography results obtained for polymer 4 are also provided in Tables 3 and 4.
[0479]
[0480]
[0481] The lithium concentration of polymer 4 was also determined by the method described in Example 3(b).
[0482] (e) Polymerization of glycerol and diethylene glycol with lithium bis(chlorosulfonyl)imide prepared in Example 2 (Polymer 5)
[0483] Polymerization was carried out by catalyst-controlled polycondensation of glycerol and diethylene glycol with lithium bis(chlorosulfonyl)imide prepared in Example 2.
[0484] The mixture containing lithium bis(chlorosulfonyl)imide of Example 2 was cooled in an ice bath for 20 minutes. The stopper was subsequently removed, and the neck of the flask was washed with a solvent to recover as much of the product as possible. The flask was subsequently sealed with a new stopper.
[0485] Next, 3 equivalents of triethylamine were added to the mixture. Subsequently, 25 mg of trifluorophenylboronic acid and 400 mg of 4-dimethylaminopyridine were added to the mixture. Next, 0.90 equivalents of diethylene glycol and 0.10 equivalents of glycerol were added, and the reaction mixture was heated at a temperature of about 100°C for about 72 hours.
[0486] The reaction mixture was continuously cooled, filtered, and precipitated in ethyl acetate. The reaction mixture was placed in an ice bath for about 30 minutes and subsequently drained.
[0487] The polymer was subsequently dissolved in a solvent mixture (2:8 volume ratio) containing isopropanol and acetone and placed in a refrigerator for about 1 hour. The mixture was then filtered to remove residual triethylamine chloride. The solvent was subsequently evaporated using a rotary evaporator at a temperature of about 60°C. Finally, the polymer was dried in a vacuum oven at a temperature of about 60°C.
[0488] Accordingly, the obtained polymer (polymer 5) was dissolved in 400 ml of water and filtered for about 7 hours by ultrafiltration through a membrane having a molecular weight cutoff limit of 1,000 DA.
[0489] Substitution of chlorine atoms was subsequently carried out by the method described in Example 3(a).
[0490] Polymer 5 proton nuclear magnetic resonance ( 1 carbon-13 nuclear magnetic resonance (H NMR) 13 3C NMR, fluorine nuclear magnetic resonance ( 19 It was analyzed using F NMR and differential scanning calorimetry (DSC).
[0491] Figure 5 shows the proton NMR spectrum obtained for the polymer obtained by the polymerization of diethylene glycol and lithium bis(chlorosulfonyl)imide prepared in Example 2 by the method as described in Example 3(a), for example.
[0492] Figures 6 to 8 show the proton NMR spectrum, carbon-13 NMR spectrum, and fluorine NMR spectrum obtained for polymer 5, respectively.
[0493] Figure 9 shows the results of differential scanning calorimetry obtained for polymer 5, and polymer 5 at the glass transition temperature (T g It is proving that ) = -73℃.
[0494] (f) Post-functionalization of the polymer prepared in Example 3(e) (Polymer 6)
[0495] Polymer 6 was prepared by post-functionalization of polymer 5 provided in Example 3(e) to introduce crosslinkable groups.
[0496] 4 g of the polymer prepared in Example 3(e) was dissolved in 25 ml of anhydrous N,N-dimethylformamide. Then, 1 ml of 2-isocyanatoethyl methacrylate was added to the solution, and the resulting mixture was heated at a temperature of about 50°C for about 5 to 12 hours under a nitrogen atmosphere.
[0497] Accordingly, the obtained polymer (polymer 6) was dissolved in 400 ml of water and filtered for about 7 hours by ultrafiltration through a membrane having a molecular weight cutoff limit of 1,000 DA.
[0498] The lithium concentration of polymer 6 was also determined by the method described in Example 3(b). A lithium concentration of 25 mol% was obtained for polymer 6.
[0499] Example 4 - Ionic Conductivity
[0500] Examples 4(a) through 4(d) relate to the preparation of polymer films for measuring the ionic conductivity of polymers as described herein by the method as described herein, whereas Examples 4(e) and 4(f) are for comparative purposes.
[0501] a) Preparation of a polymer film containing polymer 1
[0502] Ionic conductivity results were obtained for Polymer 1 prepared in Example 3(a). 1.7 g of the Polymer prepared in Example 3(a) was dissolved in a solvent mixture (80:20 by volume) containing 1.4 g of water and methanol without the addition of additional lithium salt. 10 wt% of polyvinylidene fluoride (PVdF) was added to the suspension obtained accordingly.
[0503] Continuously, the suspension was coated at 15 mm·s using a hot plate coating system (Erichsen testing instruments) with a 3 mm slit opening -1 It was applied to a substrate or support film at a speed. The polymer film obtained accordingly was dried directly during coating at a temperature of 70°C.
[0504] The polymer film was then vacuum dried in an oven at a temperature of 85°C for 48 hours to remove residual solvent.
[0505] The polymer film was continuously removed from the surface of the substrate or support film.
[0506] b) Preparation of a polymer film containing polymer 2
[0507] Ionic conductivity results were obtained for polymer 2 prepared in Example 3(b). 1.7 g of the polymer prepared in Example 3(b) was dissolved in a solvent mixture (80:20 by volume) containing 1.4 g of water and methanol without the addition of any additional lithium salt.
[0508] The suspension obtained accordingly was continuously coated at 15 mm·s using a hot plate coating system (Erichsen testing instruments) having a 3 mm slit opening -1 It was applied to a substrate or support film at a speed. The polymer film obtained accordingly was dried directly during coating at a temperature of 70°C.
[0509] The polymer film was then vacuum dried in an oven at a temperature of 85°C for 48 hours to remove residual solvent.
[0510] After drying, the polymer film was placed inside a polycarbonate (lexan) box under an inert helium atmosphere to reduce the presence of oxygen and moisture. The polymer film was then irradiated for 5 minutes with UV light (wavelength of 254 nm) positioned at a distance of about 5 cm from the polymer film.
[0511] The polymer film was continuously removed from the surface of the substrate or support film.
[0512] c) Preparation of a polymer film containing polymer 4
[0513] Ionic conductivity results were obtained for polymer 4 prepared in Example 3(d). 1.7 g of the polymer prepared in Example 3(d) was dissolved in a solvent mixture (80:20 by volume) containing 1.4 g of water and methanol without the addition of any additional lithium salt.
[0514] The suspension obtained accordingly was continuously coated at 15 mm·s using a hot plate coating system (Erichsen testing instruments) having a 3 mm slit opening -1 It was applied to a substrate or support film at a speed. The polymer film obtained accordingly was dried directly during coating at a temperature of 70°C.
[0515] The polymer film was then vacuum dried in an oven at a temperature of 85°C for 48 hours to remove residual solvent.
[0516] After drying, the polymer film was placed inside a polycarbonate (lexan) box under an inert helium atmosphere to reduce the presence of oxygen and moisture. The polymer film was then irradiated for 5 minutes with UV light (wavelength of 254 nm) positioned at a distance of about 5 cm from the polymer film.
[0517] The polymer film was continuously removed from the surface of the substrate or support film.
[0518] d) Preparation of a polymer film containing polymer 6
[0519] Ionic conductivity results were obtained for polymer 6 prepared in Example 3(f). 1.7 g of the polymer prepared in Example 3(f) was dissolved in a solvent mixture (80:20 by volume) containing 1.4 g of water and methanol without the addition of any additional lithium salt.
[0520] The suspension obtained accordingly was continuously coated at 15 mm·s using a hot plate coating system (Erichsen testing instruments) having a 3 mm slit opening -1 It was applied to a substrate or support film at a speed. The polymer film obtained accordingly was dried directly during coating at a temperature of 70°C.
[0521] The polymer film was then vacuum dried in an oven at a temperature of 85°C for 48 hours to remove residual solvent.
[0522] After drying, the polymer film was placed inside a polycarbonate (lexan) box under an inert helium atmosphere to reduce the presence of oxygen and moisture. The polymer film was then irradiated for 5 minutes with UV light (wavelength of 254 nm) positioned at a distance of about 5 cm from the polymer film.
[0523] The polymer film was continuously removed from the surface of the substrate or support film.
[0524] e) Preparation of a polymer film containing polymer 7 (comparison)
[0525] Ionic conductivity results were obtained for a polymer as described in U.S. Patent No. 7,897,674 B2 (Zaghib et al.) (US'674). 1.7 g of the polymer was dissolved in a solvent mixture (80:20 by volume) containing 1.4 g of water and methanol without the addition of any additional lithium salt.
[0526] The suspension obtained accordingly was continuously coated at 15 mm·s using a hot plate coating system (Erichsen testing instruments) having a 3 mm slit opening -1 It was applied to a substrate or support film at a speed. The polymer film obtained accordingly was dried directly during coating at a temperature of 70°C.
[0527] The polymer film was then vacuum dried in an oven at a temperature of 85°C for 48 hours to remove residual solvent.
[0528] After drying, the polymer film was placed inside a polycarbonate (lexan) box under an inert helium atmosphere to reduce the presence of oxygen and moisture. The polymer film was then irradiated for 5 minutes with UV light (wavelength of 254 nm) positioned at a distance of about 5 cm from the polymer film.
[0529] The polymer film was continuously removed from the surface of the substrate or support film.
[0530] f) Preparation of a polymer film containing polymer 8 (comparison)
[0531] Ionic conductivity results were obtained for a polymer as described in U.S. Patent No. 6,903,174 B2 (Harvey et al.) (US'174). 1.7 g of the polymer was dissolved in a solvent mixture (80:20 by volume) containing 1.4 g of water and methanol without the addition of any additional lithium salt. 0.5 wt% of 2,2-dimethoxy-2-phenylacetophenone (Irgacure™ 651) was added to the suspension thus obtained.
[0532] The suspension obtained accordingly was continuously coated at 15 mm·s using a hot plate coating system (Erichsen testing instruments) having a 3 mm slit opening -1 It was applied to a substrate or support film at a speed. The polymer film obtained accordingly was dried directly during coating at a temperature of 70°C.
[0533] The polymer film was then vacuum dried in an oven at a temperature of 85°C for 48 hours to remove residual solvent.
[0534] After drying, the polymer film was placed inside a polycarbonate (lexan) box under an inert helium atmosphere to reduce the presence of oxygen and moisture. The polymer film was then irradiated for 5 minutes with UV light (wavelength of 254 nm) positioned at a distance of about 5 cm from the polymer film.
[0535] The polymer film was continuously removed from the surface of the substrate or support film.
[0536] g) Fabrication of symmetric cells for ion conductivity measurement
[0537] The fabrication of symmetrical cells comprising the polymer films prepared in Examples 4(a) to 4(f) was carried out entirely in an anhydrous chamber having a dew point of about -55°C. The assembly of the symmetrical cells was performed in a button cell configuration. The polymer films were placed between two stainless steel inert electrodes having an active area of 2.01 cm². The symmetrical cells were assembled in the configuration shown in Table 5.
[0538]
[0539] h) Measurement of the ionic conductivity of the polymer films provided in Examples 4(a) to 4(f)
[0540] The ionic conductivity of the symmetric cells of Example 4(g) was measured by AC electrochemical impedance spectroscopy recorded with a VPM3 multichannel potentiostat. Electrochemical impedance spectroscopy was performed at temperatures ranging from 20°C to 80°C (5°C each in increase and decrease) at 200 Hz to 1 MHz.
[0541] Each electrochemical impedance measurement was obtained after the oven temperature stabilized at temperature (T).
[0542] The ionic conductivity of lithium ions was calculated from electrochemical impedance spectroscopy measurements using Equation 1:
[0543]
[0544] Here, δ is the ionic conductivity (S·cm) -1 ) and l is the thickness of the polymer film located between the two stainless steel inert electrodes, A is the contact area between the polymer and the two stainless steel electrodes, and R t is the total resistance measured by electrochemical impedance spectroscopy.
[0545] The graphs in FIGS. 10 to 15 each show the temperature (K) for the symmetrical cells (cells 1 to 6) assembled in Example 4(g). -1 Ionic conductivity (S·cm) measured as a function of ). -1 It shows the results.
[0546] Fig. 10 is 1.97 x 10 -5 S·cm -1 It indicates that the ionic conductivity value was obtained at a temperature of 50°C for cell 1 as described in Example 4(g).
[0547] Fig. 11 is 2.65 x 10 -5 S·cm -1 It indicates that the ionic conductivity value was obtained at a temperature of 50°C for cell 2 as described in Example 4(g).
[0548] Fig. 12 is 5.37 x 10 -5 S·cm -1 It indicates that the ionic conductivity value was obtained at a temperature of 50°C for cell 3 as described in Example 4(g).
[0549] Fig. 13 is 3.25 x 10 -4 S·cm -1 It indicates that the ionic conductivity value was obtained at a temperature of 50°C for cell 4 as described in Example 4(g).
[0550] Fig. 14 is 1.65 x 10 -4 S·cm -1 It indicates that the ionic conductivity value was obtained at a temperature of 50°C for cell 5 (comparison) as described in Example 4 (g).
[0551] Fig. 15 is 1.90 x 10 -4 S·cm -1 It indicates that the ionic conductivity value was obtained at a temperature of 50°C for cell 6 (comparison) as described in Example 4 (g).
[0552] Example 5 - Cyclic Voltammetry
[0553] a) Preparation of polymer films for cyclic voltammetry measurements
[0554] Cyclic voltammetry results were obtained for US'674 and US'174 patents, as well as for the polymers prepared in Examples 3(b) and 3(f), and for polyacrylonitrile (PAN) for comparison purposes.
[0555] The polymers prepared in Examples 3(b) and 3(f) and the comparative polymers were dissolved in a solvent mixture containing water and ethanol (80:20 by volume).
[0556] Once the polymers were dissolved, Ketjen™ Black was added to the mixtures in a polymer:Ketjen™ Black ratio (5:1 by weight).
[0557] The combinations of the results were continuously mixed using a ball mill to properly disperse and grind the Ketjen™ black aggregates.
[0558] Accordingly, the viscosity of the obtained mixtures was adjusted to a solvent mixture containing water and methanol (80:20 by volume).
[0559] The mixtures obtained accordingly were subsequently applied to carbon-coated aluminum current collectors using a doctor-blade coating system accompanied by a hot plate. The polymer films obtained accordingly were dried directly during coating at a temperature of 70°C.
[0560] The polymer films were subsequently dried in an oven under vacuum at a temperature of 85°C for 48 hours to remove residual solvent.
[0561] b) Fabrication of symmetric cells for cyclic voltammetry measurements
[0562] The fabrication of symmetrical cells containing the polymer films prepared in Example 5(a) was carried out entirely in an anhydrous chamber having a dew point of about -55°C. The symmetrical cells were assembled into a button cell configuration having an active area of 2.01 cm². The symmetrical cells were assembled according to the configuration shown in Table 6.
[0563]
[0564] c) Cyclic voltammetry
[0565] The electrochemical stability in oxidation of symmetric cells as described in Example 5(b) was measured using a VMP-3 type potentiometer.
[0566] FIG. 16 shows 2.7 V to 4.3 V versus Li / Li + This shows the cyclic voltammetry results obtained for cell 7 (comparison cell) (solid line) recorded at a scan rate of 0.067 mV / s.
[0567] FIG. 17 shows 2.5 V to 5 V versus Li / Li +Figure 17 shows the cyclic voltammetry results obtained for cell 7 (comparison cell) recorded at a scan rate of 0.067 mV / s. Figure 17 shows the polymer oxidation at approximately 4.37 V versus Li / Li + It indicates that it starts at the potential.
[0568] FIG. 18 shows 2.5 V to 5 V versus Li / Li + This shows the cyclic voltammetry results obtained for cell 9 (solid line) and cell 10 (dashed line) recorded at a scan rate of 0.067 mV / s.
[0569] FIG. 19 shows 2.5 V to 5 V versus Li / Li + Figure 19 shows the cyclic voltammetry results obtained for cell 7 (comparison cell) (dotted line), cell 10 (dotted line), cell 9 (dashed line), and cell 11 (comparison cell) (solid line) recorded at a scan rate of 0.067 mV / s. Figure 19 shows the results obtained during the first cycle.
[0570] Various modifications may be made to any of the embodiments described above without departing from the scope of the invention as considered. References, patents, or scientific literature records mentioned herein are incorporated herein by reference in their entirety for all purposes.
Claims
Claim 1 An ionic polymer comprising at least one repeating unit comprising a reaction product between at least one compound of Formula 1 comprising at least two functional groups and a metal bis(halosulfonyl)imide of Formula 2: Here, A is a linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkylene oxy C1-C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1-C 10 A substituted or unsubstituted organic group selected from alkylenes, linear or branched polyethers, and linear or branched polyesters; X1 and X2 are functional groups selected independently and in each case from hydroxyl groups, thiol groups, and amine groups; X3 and X4 are halogen atoms selected independently from F, Cl, Br, and I, respectively; M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ The alkali metal ion or alkaline earth metal ion selected from the group consisting of ions, and the ionic polymer further comprises at least one crosslinkable functional group present at the end of the chain, on the side chain, or in a combination thereof. Claim 2 In claim 1, the crosslinkable functional group is C1-C 10 Alkyl-acrylate group, C1-C 10 Alkyl-methacrylate group, oxycarbonylamino-C1-C 10 Alkyl-methacrylate group, oxycarbonylamino-C1-C 10 Alkyl-acrylate group, carbonylamino-C1-C 10 Alkyl-methacrylate group and carbonylamino-C1-C 10 Ionic polymer selected from alkyl-acrylate groups. Claim 3 An ionic polymer according to claim 1 or 2, wherein X3 and X4 are both chlorine atoms. Claim 4 In paragraph 1 or 2, M n+ is Na + , K + and Li + An ionic polymer, which is an alkali metal ion selected from a group of ions. Claim 5 In Paragraph 4, M n+ is Li + Ionic, ionic polymer. Claim 6 In claim 1 or 2, X1 and X2 are both hydroxyl-derived ionic polymers. Claim 7 In claim 6, the compound of Chemical Formula 1 is an ionic polymer selected from glycerol, alkanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol, 1,2-butanediol, 2,3-butanediol, 1,3-butanediol, 1,2-pentanediol, ethohexadiol, p-methane-3,8-diol, 2-methyl-2,4-pentanediol, polycaprolactone diol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, polyethylene glycol, 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediol, and combinations of at least two of these. Claim 8 In claim 7, the compound of Chemical Formula 1 is an ionic polymer, which is a glycol. Claim 9 In claim 7, the compound of Chemical Formula 1 is an ionic polymer, wherein the compound is glycerol. Claim 10 In claim 1 or 2, the compound of Chemical Formula 1 is selected from alkanediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,8-octanediamine, 1,2-propanediamine, 1,2-butanediamine, 2,3-butanediamine, 1,3-butanediamine, 1,2-pentanediamine, 2,4-diamino-2-methylpentane, ethylenediamine, 1,8-diamino-3,6-dioxaoctane, 1,11-diamino-3,6,9-trioxaundecane, 4,9-dioxa-1,12-dodecanediamine, 1,14-diamino-3,6,9,12-tetraoxatetradecane, poly(ethylene glycol)diamine, and combinations of at least two of these. Ionic polymer. Claim 11 In claim 10, the compound of Chemical Formula 1 is an ionic polymer selected from the compounds of Chemical Formulas 4(a) to 4(c), 5(a) and 6(a) below: Here, m is a number in the range of 1 to 68; n, o and p are numbers selected such that the number average molecular weight of the polyether is 220 g / mol to 2,000 g / mol, including upper and lower limits; o is a number in the range of 2 to 39; and q and r are numbers in the range of 1 to 10. Claim 12 In item 10, the compound of chemical formula 1 is chemical formula H2NCH2CH2(OCH2CH2) n An ionic polymer that is a poly(ethylene glycol) diamine of NH2, where n is 1 or 2. Claim 13 In paragraph 1, A is an optionally substituted linear or branched C1-C 10 It is an alkylene, and the compound of chemical formula 1 is a compound of chemical formula 3 and: Here, X1 and X2 are as defined in claim 1; R1 and R2 are independently and in each case a halogen atom selected from hydrogen atoms, hydroxyl groups, thiol groups, amine groups, F, Cl, Br, and I, and C1-C 10 Alkyl, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-acrylate, aminocarbonyl-C1-C 10 Alkyl-methacrylate, aminocarbonyl-C1-C 10 Alkyl-acrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 An ionic polymer selected from linear or branched substituents selected from alkyl-acrylates; and l is a number in the range of 1 to 10. Claim 14 In paragraph 13, X1 and X2 are both hydroxyl-derived ionic polymers. Claim 15 In paragraph 13 or 14, R1 and R2 are independently and in each case a hydrogen atom, a hydroxyl group, a thiol group, an amine group, a fluorine atom, and C1-C 10 Alkyl, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 An ionic polymer selected from linear or branched substituents selected from alkyl-acrylates. Claim 16 In claim 1, A is linear or branched and optionally substituted poly(C1-C 10 Alkyleneoxy)C1-C 10 It is an alkylene, and the compound of chemical formula 1 is a compound of chemical formula 4, and: Herein, X1 and X2 are as defined in claim 1; and m is an ionic polymer, which is a number within the range of 1 to 68. Claim 17 In paragraph 16, X1 and X2 are both hydroxyl-derived ionic polymers. Claim 18 In paragraph 16 or 17, m is an ionic polymer, which is a number within the range of 1 to 10. Claim 19 In claim 1, A is a linear or branched and optionally substituted polyether, and the compound of Formula 1 is a compound of Formula 5: Here, X1 and X2 are as defined in Paragraph 1; R3, R4, and R5 are independently and in each case C1-C 10 An ionic polymer selected from alkyl groups; n, o, and p are selected such that the number average molecular weight of the polyether is about 220 g / mol to about 2,000 g / mol, including upper and lower limits; n and p are selected such that the sum (n + p) is within the range of about 1 to about 6; and o is a number within the range of about 2 to about 39. Claim 20 In paragraph 19, R3, R4, and R5 are methyl-based ionic polymers. Claim 21 In paragraph 19 or 20, X1 and X2 are both amine-derived ionic polymers. Claim 22 In claim 1, A is an optionally substituted aliphatic polyester such as polycaprolactone, and the compound of Formula 1 is a compound of Formula 7: Here, t and u are numbers within the range of 1 to 10, ionic polymer. Claim 23 In claim 1, the ionic polymer comprises at least one repeating unit of formula 8(a) or is a polymer of formula 8(b): Here, A is independently and in each case, linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkylene oxy C1-C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1-C 10 A substituted or unsubstituted organic group selected from alkylenes, linear or branched polyethers, and linear or branched polyesters; X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups; R6 is selected from hydroxyl groups, thiol groups, amine groups, and R7-X5-A-X6- groups; R7 is independently selected from acrylates, methacrylates, and C1-C in each case. 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonyl-C1-C 10 Alkyl-methacrylate carbonyl-C1-C 10 Alkyl-acrylate, carbonyloxy-C1-C 10 Alkyl-methacrylate, carbonyloxy-C1-C 10 Alkyl-acrylate, carbonylamino-C1-C 10 Alkyl-methacrylate and carbonylamino-C1-C 10 A crosslinkable group selected from alkyl-acrylates; M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ An alkali metal ion or alkaline earth metal ion selected from the group consisting of ions; and v is a number selected such that the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, of an ionic polymer. Claim 24 In Paragraph 23, M n+ is Na + , K + and Li + An ionic polymer, which is an alkali metal ion selected from a group of ions. Claim 25 In Article 23 or 24, M n+ is Li + Ionic, ionic polymer. Claim 26 In paragraph 23, X5 and X6 are both oxygen atoms, an ionic polymer. Claim 27 In paragraph 23, X5 and X6 are ionic polymers in which both are sulfur atoms. Claim 28 In paragraph 23, X5 and X6 are both NH-based ionic polymers. Claim 29 In paragraph 23, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 30 In claim 1, the ionic polymer comprises at least one repeating unit of Formula 9: Here, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ Alkali metal ions or alkaline earth metal ions selected from the group consisting of ions; X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups; R1 and R2 are independently and, in each case, halogen atoms selected from hydrogen atoms, hydroxyl groups, thiol groups, amine groups, F, Cl, Br, and I, and C1-C 10 Alkyl, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-acrylate, aminocarbonyl-C1-C 10 Alkyl-methacrylate, aminocarbonyl-C1-C 10 Alkyl-acrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 An ionic polymer selected from linear or branched substituents selected from alkyl-acrylates; l is a number within the range of 1 to 10; and w is a number selected such that the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits. Claim 31 In Paragraph 30, M n+ is Na + , K + and Li + An ionic polymer, which is an alkali metal ion selected from a group of ions. Claim 32 In Article 30 or 31, M n+ is Li + Ionic, ionic polymer. Claim 33 In paragraph 30, R1 and R2 are independently and in each case a hydrogen atom, a hydroxyl group, a thiol group, an amine group, a fluorine atom, and C1-C 10 Alkyl, C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylates and oxycarbonylamino-C1-C 10 An ionic polymer selected from linear or branched substituents selected from alkyl-acrylates. Claim 34 In paragraph 30, X5 and X6 are both oxygen atoms, an ionic polymer. Claim 35 In paragraph 30, X5 and X6 are both sulfur atoms, an ionic polymer. Claim 36 In Clause 30, X5 and X6 are both NH-based ionic polymers. Claim 37 An ionic polymer according to claim 30, wherein the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 60,000 g / mol, including upper and lower limits. Claim 38 In claim 1, the ionic polymer comprises at least one repeating unit of Formula 10: Here, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ An ionic polymer, wherein the alkali metal ion or alkaline earth metal ion is selected from a group consisting of ions; X5 and X6 are each independently selected from an oxygen atom, a sulfur atom, and a -NH group; m is a number within the range of 1 to 68; and x is a number selected such that the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits. Claim 39 In Paragraph 38, M n+ is Na + , K + and Li + An ionic polymer, which is an alkali metal ion selected from a group of ions. Claim 40 In Article 38 or 39, M n+ is Li + Ionic, ionic polymer. Claim 41 In paragraph 38, an ionic polymer in which X5 and X6 are both oxygen atoms. Claim 42 In paragraph 38, X5 and X6 are both sulfur atoms, an ionic polymer. Claim 43 In paragraph 38, X5 and X6 are both NH-based ionic polymers. Claim 44 An ionic polymer according to claim 38, wherein the number average molecular weight of the ionic polymer is between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 45 In claim 1, the ionic polymer comprises at least one repeating unit of Formula 11: Here, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ Alkali metal ions or alkaline earth metal ions selected from a group consisting of ions; X5 and X6 are each independently selected from oxygen atoms, sulfur atoms, and -NH groups; R3, R4, and R5 are independently and in each case C1-C 10 An ionic polymer selected from alkyl groups; n and p are selected such that the sum (n + p) is in the range of about 1 to about 6; o is a number in the range of about 2 to about 39; and y is a number selected such that the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits. Claim 46 In paragraph 45, M n+ is Na + , K + and Li + An ionic polymer, which is an alkali metal ion selected from a group of ions. Claim 47 In paragraph 45 or 46, M n+ is Li + Ionic, ionic polymer. Claim 48 In paragraph 45, R3, R4, and R5 are methyl-based ionic polymers. Claim 49 In paragraph 45, X5 and X6 are both oxygen atoms, an ionic polymer. Claim 50 In paragraph 45, X5 and X6 are both sulfur atoms, an ionic polymer. Claim 51 In paragraph 45, X5 and X6 are both -NH-based ionic polymers. Claim 52 An ionic polymer according to claim 45, wherein the number average molecular weight of the ionic polymer is between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 53 In claim 1, the ionic polymer comprises at least one repeating unit of Formula 12: Here, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ An ionic polymer, wherein the alkali metal ion or alkaline earth metal ion is selected from the group consisting of ions; t and u are numbers ranging from 1 to 10; and z is a number selected such that the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits. Claim 54 In Paragraph 53, M n+ is Na + , K + and Li + An ionic polymer, which is an alkali metal ion selected from a group of ions. Claim 55 In Article 53 or 54, M n+ is Li + Ionic, ionic polymer. Claim 56 In paragraph 53, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 57 In claim 1, the ionic polymer comprises at least one fragment of Formula 13: Here, x is a number selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for the ionic polymer. Claim 58 An ionic polymer according to claim 57, wherein the number average molecular weight of the ionic polymer is about 8,000 g / mol to about 60,000 g / mol, including upper and lower limits. Claim 59 In claim 1, the ionic polymer comprises at least one fragment of Formula 14: Here, x is a number selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for the ionic polymer. Claim 60 In claim 59, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 61 In claim 1, the ionic polymer comprises at least one fragment of Formula 15: Here, X5 and X6 are each independently selected from oxygen atoms, sulfur atoms and -NH groups; and x is a number selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for an ionic polymer. Claim 62 In paragraph 61, an ionic polymer in which X5 and X6 are both oxygen atoms. Claim 63 In paragraph 61, X5 and X6 are both sulfur atoms, an ionic polymer. Claim 64 In Clause 61, X5 and X6 are both NH-based ionic polymers. Claim 65 An ionic polymer according to claim 61, wherein the number average molecular weight of the ionic polymer is between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 66 In claim 1, the ionic polymer comprises at least one fragment of Formula 16: Here, X5 and X6 are each independently selected from oxygen atoms, sulfur atoms and -NH groups; and x is a number selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for an ionic polymer. Claim 67 In paragraph 66, X5 and X6 are both oxygen atoms, an ionic polymer. Claim 68 In paragraph 66, X5 and X6 are both sulfur atoms, an ionic polymer. Claim 69 In paragraph 66, X5 and X6 are both -NH-based ionic polymers. Claim 70 In claim 66, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 71 In claim 1, the ionic polymer comprises at least one fragment of Formula 17: Here, X5 and X6 are each independently selected from oxygen atoms, sulfur atoms and -NH groups; and x is a number selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for an ionic polymer. Claim 72 In paragraph 71, an ionic polymer in which X5 and X6 are both oxygen atoms. Claim 73 In paragraph 71, X5 and X6 are both sulfur atoms, an ionic polymer. Claim 74 In paragraph 71, X5 and X6 are both -NH-based ionic polymers. Claim 75 An ionic polymer according to claim 71, wherein the number average molecular weight of the ionic polymer is between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 76 In claim 1, the ionic polymer comprises at least one fragment of Formula 18: Here, X5 and X6 are each independently selected from oxygen atoms, sulfur atoms and -NH groups; and x is a number selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for an ionic polymer. Claim 77 In paragraph 76, X5 and X6 are both oxygen atoms, an ionic polymer. Claim 78 In paragraph 76, X5 and X6 are both sulfur atoms, an ionic polymer. Claim 79 In Clause 76, X5 and X6 are both -NH-based ionic polymers. Claim 80 In claim 76, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 81 In claim 1, the ionic polymer comprises at least one fragment of Formula 19: Here, w is a number selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for the ionic polymer. Claim 82 An ionic polymer according to claim 81, wherein the number average molecular weight of the ionic polymer is between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 83 In claim 1, the ionic polymer comprises at least one fragment of Formula 20: Here, w is a number selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for the ionic polymer. Claim 84 In paragraph 83, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 85 In claim 1, the ionic polymer comprises at least one fragment of Formula 21: Here, n and p are selected such that the sum (n + p) is in the range of about 1 to about 6; o is a number in the range of about 2 to about 39; and y is a number selected such that the number average molecular weight of the ionic polymer is in the range of about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, of an ionic polymer. Claim 86 An ionic polymer according to claim 85, wherein the number average molecular weight of the ionic polymer is between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 87 In claim 1, the ionic polymer comprises at least one fragment of Formula 22: Here, n and p are selected such that the sum (n + p) is in the range of about 1 to about 6; o is a number in the range of about 2 to about 39; and y is a number selected such that the number average molecular weight of the ionic polymer is in the range of about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, of an ionic polymer. Claim 88 In claim 87, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 89 In claim 1, the ionic polymer comprises at least one fragment of Formula 23: Here, n and p are selected such that the sum (n + p) is in the range of about 1 to about 6; o is a number in the range of about 2 to about 39; and y is a number selected such that the number average molecular weight of the ionic polymer is in the range of about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, of an ionic polymer. Claim 90 In claim 89, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 91 In claim 1, the ionic polymer comprises at least one fragment of Formula 24: Here, n and p are selected such that the sum (n + p) is in the range of about 1 to about 6; o is a number in the range of about 2 to about 39; and y is a number selected such that the number average molecular weight of the ionic polymer is in the range of about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, of an ionic polymer. Claim 92 An ionic polymer according to claim 91, wherein the number average molecular weight of the ionic polymer is between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 93 In claim 1, the ionic polymer comprises at least one fragment of Formula 25: Here, n and p are selected such that the sum (n + p) is in the range of about 1 to about 6; o is a number in the range of about 2 to about 39; and y is a number selected such that the number average molecular weight of the ionic polymer is in the range of about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, of an ionic polymer. Claim 94 In paragraph 93, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 95 In claim 1, the ionic polymer comprises at least one fragment of Formula 26: Here, w and x are numbers selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for the ionic polymer. Claim 96 An ionic polymer according to claim 95, wherein the number average molecular weight of the ionic polymer is between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 97 In claim 1, the ionic polymer comprises at least one fragment of Formula 27: Here, w and x are numbers selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for the ionic polymer. Claim 98 In claim 97, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 99 In claim 1, the ionic polymer comprises at least one fragment of Formula 28: Here, w and x are numbers selected such that the number average molecular weight of the ionic polymer is from about 8,000 g / mol to about 150,000 g / mol, including upper and lower limits, for the ionic polymer. Claim 100 In claim 99, the ionic polymer has a number average molecular weight between about 8,000 g / mol and about 60,000 g / mol, including upper and lower limits. Claim 101 A polymer composition comprising at least one ionic polymer according to claim 1. Claim 102 In claim 101, the polymer composition further comprises additional components or additives. Claim 103 In claim 102, the additional component or additive is a polymer composition selected from ion conductors, inorganic particles, glass particles, ceramic particles, and a combination of at least two of these. Claim 104 A polymer composition according to claim 102 or 103, wherein the additional component or additive is a filler additive. Claim 105 In claim 104, the filler additive is a polymer composition selected from titanium dioxide (TiO2), alumina (Al2O3), and silicon dioxide (SiO2) particles or nanoparticles. Claim 106 In claim 101, the polymer composition is a solid polymer electrolyte composition. Claim 107 In claim 101, the polymer composition is a polymer composition that is a binder for an electrode material. Claim 108 In claim 101, the polymer composition is a polymer composition used in an electrochemical cell. Claim 109 In claim 101, the polymer composition is a polymer composition used in a supercapacitor. Claim 110 In claim 109, the polymer composition, wherein the supercapacitor is a carbon-carbon supercapacitor. Claim 111 In claim 101, the polymer composition is a polymer composition used in electrochromic materials. Claim 112 A solid polymer electrolyte composition comprising an ionic polymer according to claim 1. Claim 113 In claim 112, the solid polymer electrolyte composition further comprises at least one salt. Claim 114 In Clause 113, the above salt is an ionic salt, a solid polymer electrolyte composition. Claim 115 A solid polymer electrolyte composition according to claim 114, wherein the ion salt is selected from lithium salt, sodium salt, potassium salt, calcium salt and magnesium salt. Claim 116 In claim 115, the above-mentioned ionic salt is a lithium salt, a solid polymer electrolyte composition. Claim 117 In claim 116, the lithium salt is lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanomidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3)(LiTf), lithium fluoroalkyl phosphate A solid polymer electrolyte composition selected from Li[PF3(CF2CF3)3](LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4](LiTFAB), lithium bis(1,2-benzenediolatto(2-)-O,O')borate Li[B(C6O2)2](LiBBB), and combinations of at least two of these. Claim 118 In claim 112, the solid polymer electrolyte composition further comprises additional components or additives. Claim 119 In claim 118, the additional component or additive is a solid polymer electrolyte composition selected from an ion conductor material, inorganic particles, glass particles, ceramic particles, and a combination of at least two of these. Claim 120 A solid polymer electrolyte comprising an ionic polymer according to claim 1. Claim 121 Electrode material comprising an electrochemically active material and an ionic polymer according to claim 1. Claim 122 In Clause 121, the above polymer is an electrode material that is a binder. Claim 123 In claim 121 or 122, the electrochemically active material is an electrode material in the form of particles. Claim 124 In claim 121, the electrochemically active material is an electrode material selected from metal oxide, lithium metal oxide, metal phosphate, lithiated metal phosphate, titanate, and lithium titanate. Claim 125 In claim 124, the metal of the electrochemically active material is an electrode material selected from titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), and combinations of at least two of these. Claim 126 In claim 121, the electrode material further comprises at least one electrically conductive material. Claim 127 In claim 126, the electrically conductive material is an electrode material selected from carbon black, acetylene black, graphite, graphene, carbon fiber, carbon nanofiber, carbon nanotube, and a combination of at least two of these. Claim 128 In paragraph 127, the electrically conductive material is an electrode material, which is acetylene black. Claim 129 In paragraph 121, the electrode material further comprises additional components or additives. Claim 130 In paragraph 129, the additional component or additive is an electrode material selected from ion conductors, inorganic particles, glass or ceramic particles, nanoceramics, and salts. Claim 131 In paragraph 129 or 130, the additional component or additive is an electrode material selected from Al2O3, TiO2 and SiO2. Claim 132 In Clause 121, the electrode material is an electrode material that is an anode material. Claim 133 In Clause 121, the electrode material is a negative electrode material. Claim 134 In paragraph 133, the electrochemically active material is an electrode material, which is lithium titanate. Claim 135 In paragraph 134, the above lithium titanate is an electrode material that is carbon-coated lithium titanate. Claim 136 An electrode comprising an electrode material according to claim 121 on a current collector. Claim 137 An electrochemical cell comprising a negative electrode, a positive electrode, and an electrolyte, wherein at least one of the negative electrode, the positive electrode, and the electrolyte comprises an ionic polymer according to claim 1. Claim 138 An electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein at least one of the negative electrode and the positive electrode is an electrochemical cell as defined in claim 136. Claim 139 An electrochemical cell comprising a cathode, an anode, and a solid polymer electrolyte as defined in paragraph 120. Claim 140 An electrochemical capacitor comprising at least one electrochemical cell according to paragraph 137. Claim 141 In claim 140, the electrochemical capacitor is an electrochemical capacitor that is a battery selected from lithium batteries, lithium-ion batteries, sodium batteries, sodium-ion batteries, magnesium batteries, and magnesium-ion batteries. Claim 142 In paragraph 141, the battery is an electrochemical capacitor that is a lithium or lithium-ion battery. Claim 143 A method for preparing an ionic polymer according to claim 1, comprising: (i) preparing a metal bis(halosulfonyl)imide of Formula 2; and (ii) reacting at least one compound of Formula 1 with the metal bis(halosulfonyl)imide of Formula 2; the method comprising. Claim 144 In paragraph 143, the method further comprises the step of manufacturing bis(halosulfonyl)imide. Claim 145 In claim 144, the step of preparing the bis(halosulfonyl)imide is carried out by a reaction between a sulfamic acid and a halosulfonic acid in the presence of at least one halogenating agent. Claim 146 In claim 145, the halogenating agent is selected from phosphorus trichloride, phosphorus pentachloride, thionyl chloride, thionyl fluoride, phosphorus oxychloride, and oxalyl chloride. Claim 147 A method according to claim 145 or 146, wherein the halogenating agent is thionyl chloride. Claim 148 In paragraph 145, the above halosulfonic acid is chlorosulfonic acid. Claim 149 A method according to claim 144, wherein the step of preparing bis(halosulfonyl)imide is carried out at a temperature within the range of about 60°C to about 150°C, or about 70°C to about 145°C, or about 80°C to about 140°C, or about 90°C to about 100°C, or about 110°C to about 140°C, or about 120°C to about 140°C, or about 125°C to about 140°C, or about 125°C to about 135°C, including upper and lower limits. Claim 150 In claim 144, the step of preparing the metal bis(halosulfonyl)imide is performed at a temperature of about 130°C for a period of about 24 hours, including upper and lower limits, in a method. Claim 151 In paragraph 144, the method wherein the bis(halosulfonyl)imide is bis(chlorosulfonyl)imide. Claim 152 In claim 143, the step of preparing a metal bis(halosulfonyl)imide is carried out by a metallization reaction between the bis(halosulfonyl)imide and at least one metallizing agent, optionally in the presence of a solvent. Claim 153 In claim 152, the metallizing agent comprises an alkali metal selected from lithium, sodium, potassium, calcium, and magnesium. Claim 154 In paragraph 153, the metallizing agent comprises an alkali metal selected from lithium, sodium, and potassium. Claim 155 In paragraph 154, the metallizing agent is a lithiating agent, method. Claim 156 In paragraph 155, the lithiating agent is lithium hydroxide, lithium carbonate, lithium bicarbonate, lithium hydride, lithium chloride, lithium bromide, lithium iodide, and the chemical formula RCO2Li (where R is a linear or branched C1-C 10 A method selected from lithium carboxylates, lithium oxalates, and metallic lithium (which are alkyl groups or aromatic hydrocarbons). Claim 157 A method according to claim 155 or 156, wherein the lithiating agent is lithium chloride (LiCl). Claim 158 The method according to claim 152, wherein the solvent is selected from N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethylacetamide, carbon tetrachloride, chloroform, acetonitrile, tetrahydrofuran, and at least two miscible combinations thereof. Claim 159 In paragraph 158, the method wherein the solvent is N,N-dimethylformamide. Claim 160 A method according to claim 143, wherein the step of preparing a metal bis(halosulfonyl)imide is carried out at a temperature within the range of about 20°C to about 150°C, or about 30°C to about 135°C, or about 40°C to about 130°C, or about 50°C to about 125°C, or about 60°C to about 120°C, or about 70°C to about 115°C, or about 80°C to about 110°C, or about 90°C to about 105°C, including upper and lower limits. Claim 161 In paragraph 143, the step of preparing the metal bis(halosulfonyl)imide is carried out at a temperature of about 100°C. Claim 162 A method according to claim 143, wherein the step of producing a metal bis(halosulfonyl)imide is performed for a time within the range of about 10 hours to about 48 hours, or about 10 hours to about 24 hours, or about 12 hours to about 24 hours, including upper and lower limits. Claim 163 In claim 162, the step of producing a metal bis(halosulfonyl)imide is performed for a time within the range of about 12 hours to about 24 hours, including upper and lower limits. Claim 164 In claim 143, the step of reacting at least one compound of Formula 1 with a metal bis(halosulfonyl)imide of Formula 2 is a polymerization step. Claim 165 In paragraph 164, the method wherein the polymerization is carried out by polycondensation. Claim 166 In paragraph 164, the polymerization is carried out by polyesterization. Claim 167 In paragraph 166, the polyesterization is carried out by a Fischer esterification reaction. Claim 168 In paragraph 166, the polyesterization is carried out by a Steglich esterification reaction. Claim 169 In claim 143, the step of reacting at least one compound of Formula 1 with a metal bis(halosulfonyl)imide of Formula 2 is carried out in the presence of a solvent. Claim 170 In claim 169, the solvent is selected from N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethylacetamide, carbon tetrachloride, chloroform, acetonitrile, tetrahydrofuran, and at least two miscible combinations thereof. Claim 171 In paragraph 170, the method wherein the solvent is N,N-dimethylformamide. Claim 172 A method according to claim 164, wherein the polymerization step is carried out in the presence of at least one base, and in the presence of at least one polymerization catalyst, at least one co-catalyst, at least one acylation catalyst, or a combination of at least two of these. Claim 173 In claim 172, the polymerization catalyst is selected from the group consisting of acidic catalysts, nucleophilic catalysts, and boron-based catalysts. Claim 174 In paragraph 173, the above acidic catalyst is a Lewis acid catalyst. Claim 175 In claim 173, the nucleophilic catalyst is selected from the group consisting of 4-dimethylaminopyridine, pyridine, and other pyridine derivatives. Claim 176 In paragraph 175, the method wherein the nucleophilic catalyst is 4-dimethylaminopyridine. Claim 177 In paragraph 173, the boron-based catalyst is a boric acid-based catalyst, a boronic acid-based catalyst, or a boric acid-based catalyst. Claim 178 The method according to claim 173, wherein the polymerization catalyst is selected from diarylboric acid of the formula Ar2BOH (where Ar is an aryl group), diphenylboric acid, trifluorophenylboric acid, 9H-9-bora-10-thianthracen-9-ol, 10H-phenoxaborinine-10-ol, boron tribromide, boron trichloride, acyl fluoroborates, triethyloxonium fluoroborate, boron trifluoride etherate, boron trifluoride, tris(pentafluorophenyl)borane, and, if compatible, a combination of at least two of these. Claim 179 In paragraph 172, the method wherein the base is selected from the group consisting of triethylamine, N,N-diisopropylethylamine, pyridine, and pyridine derivatives. Claim 180 In paragraph 179, the above base is triethylamine, method. Claim 181 In paragraph 143, the method further comprises a post-functionalization or post-polymerization modification step. Claim 182 A method according to claim 181, wherein the post-functionalization or post-polymerization modification step is performed to introduce at least one crosslinkable functional group. Claim 183 In claim 182, the post-functionalization or post-polymerization modification step is carried out by a reaction between at least one functional group and at least one precursor of a crosslinkable functional group. Claim 184 In claim 182 or 183, the crosslinkable functional group is an acrylate, a methacrylate, a C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-methacrylate, oxycarbonyl-C1-C 10 Alkyl-acrylate, aminocarbonyl-C1-C 10 Alkyl-methacrylate aminocarbonyl-C1-C 10 Alkyl-acrylate, oxycarbonylamino-C1-C 10 Alkyl-methacrylate, oxycarbonylamino-C1-C 10 Alkyl-acrylate, carbonyloxy-C1-C 10 Alkyl-methacrylate, carbonyloxy-C1-C 10 Alkyl-acrylate, carbonylamino-C1-C 10 Alkyl-methacrylate, and carbonylamino-C1-C 10 A method selected from alkyl-acrylates. Claim 185 In paragraph 143, the method further comprises a separation or purification step. Claim 186 In paragraph 185, the separation or purification step is carried out by liquid chromatography or filtration. Claim 187 In paragraph 186, the above liquid chromatography method is stereoexclusion chromatography. Claim 188 In paragraph 186, the above filtration method is a membrane filtration method. Claim 189 In paragraph 188, the above membrane filtration method is a membrane nanofiltration method or a membrane ultrafiltration method. Claim 190 In paragraph 189, the above membrane filtration method is a membrane ultrafiltration method. Claim 191 In claim 190, the method wherein the membrane has a molecular weight cutoff limit of 1,000 DA. Claim 192 A method for preparing a polymer composition according to claim 101, comprising: (i) preparing a metal bis(halosulfonyl)imide of Formula 2; and (ii) reacting at least one compound of Formula 1 with the metal bis(halosulfonyl)imide of Formula 2; the method comprising. Claim 193 In claim 192, the method further comprises the step of coating a polymer composition. Claim 194 In claim 193, the coating step is performed by at least one method selected from the doctor blade coating method, the comma coating method, the reverse comma coating method, the printing method, the gravure coating method, and the slot-die coating method. Claim 195 In claim 194, the coating step is performed by at least one method selected from the doctor blade coating method and the slot-die coating method. Claim 196 In claim 192, the method further comprises the step of drying the polymer composition to remove residual solvent, water, or a combination thereof. Claim 197 A method according to claim 196, wherein the drying step of the polymer composition and the coating step of the polymer composition are performed simultaneously. Claim 198 In paragraph 143, the method further comprises a crosslinking step. Claim 199 In claim 198, the crosslinking step is performed by UV irradiation, by heat treatment, by microwave irradiation, under an electron beam, by gamma ray irradiation, or by X-ray irradiation. Claim 200 In claim 199, the crosslinking step is performed by UV irradiation, by heat treatment, or under an electron beam. Claim 201 A method according to claim 198, wherein the crosslinking step is carried out in the presence of a crosslinking agent, a thermal initiator, a photoinitiator, a catalyst, a plasticizer, or a combination of at least two of these. Claim 202 Method of claim 201, wherein the crosslinking agent is 2,2-dimethoxy-2-phenylacetophenone.
Citation Information
Patent Citations
Composite solid electrolyte of lithium salts of sulfonimide and its preparing process
CN1320979A
Solid polymer electrolyte
JP1998168194A